Biomass-derived biochar for CO2 adsorption: Physicochemical design, adsorption kinetics, isotherm modeling, and carbon-management perspectives - Baala H. Anandapadmanaban; Shu-Hui Liu; Chi-Wen Lin; Tzung-Han Chou; Rabia Tasaduq Hussain (Biomass and Bioenergy, 2027)

Asymptotic solutions of transient waves generated by a wavemaker in water of uniform depth - Haiqi Fang; Peter H.-Y. Lo; Pengzhi Lin; Philip L.-F. Liu (Wave Motion, 2027)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Future directions in oil spill modeling - Tor Nordam; Ana J. Abascal; Germán Aragón; Hossein Babaei; Christopher H. Barker; Kuo-Hsien Chang; Knut-Frode Dagestad; Rodrigo Duran; Deborah French-McCay; Melissa Gloekler; Aurelien Hospital; Panagiota Keramea; et al. (Ocean Modelling, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Associations of neighborhood racial and ethnic, economical, and educational segregation with breast cancer risk: The Multiethnic ohort Study - Ugonna Ihenacho; Jenna Khan-Gates; Katherine Lin; Janine V. Abe; Pushkar P. Inamdar; Juan Yang; Yuqing Li; Meera Sangaramoorthy; Christopher A. Haiman; Loïc Le Marchand; Lynne R. Wilkens; Scarlett Lin Gomez; et al. (Cancer Causes & Control, 2026)
Purpose Residential segregation is recognized as an upstream driver of poor health, yet few studies have evaluated its impact on breast cancer incidence at a local level. We examined associations of neighborhood residential segregation with breast cancer (BC) incidence in the Multiethnic Cohort Study (MEC). Methods Measures of Index of Concentration at the Extremes were developed to assess residential segregation by income, education, race and ethnicity, and racialized income. A prospective study (1993–1996 through December 2019) was conducted to examine associations of these measures and breast cancer incidence for 101,785 African American, Japanese American, Latina, Native Hawaiian, and White female participants in the MEC, aged 45–75 years at baseline and residing in California and Hawai‘i. Multivariable Cox regression was conducted to evaluate the associations of several residential segregation measures with breast cancer incidence (cases = 7,381) adjusting for demographic, lifestyle, and reproductive factors. Results In California, BC risk was higher for females residing in neighborhoods with the highest compared to lowest concentration of privilege by income segregation (quintile 5 [Q5] vs. Q1: hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.00–1.25, P trend = 0.001) and education segregation (Q5 vs. Q1: HR 1.15, 95% CI 1.01–1.31; P trend = 0.01). For Latina females, risks increased with increasing privilege for measures of income, education, race and ethnicity, and racialized income residential segregation ( P trends < 0.05). No associations were observed in Hawai‘i. Conclusion In California, residential economic privilege was independently associated with increased BC risk. Future studies should examine neighborhood- and individual-level pathways placing females residing in privileged areas at greater risk.

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Retraction Note: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Structural elucidation and distribution pattern of glucuronic acid in β-glucan from Hypsizygus marmoreus using glycosidase hydrolysis - Yunhe Qu; Ziyan Sun; Xiushi Jia; Yuanning Wang; Xing Yang; Yunmei Ma; Kevin H. Mayo; Lin Sun; Dongfang Shi; Yifa Zhou (Carbohydrate Polymers, 2026)

A comprehensive review of phage immobilization and encapsulation for the application in food safety - Pankaj Koirala; Yen-Te Liao; Meng-Wei Lin; Shyam S. Sablani; Vivian C. H. Wu (Critical Reviews in Food Science and Nutrition, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The importance of pro-environmental behavior in advancing sustainable tourism - Tiling Chen; Chao Ye; Lingjie Tang; H. Elhosiny Ali; Luning Lin; Youyou Zhu; Sana Togroi (Journal of Outdoor Recreation and Tourism, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Cross‐Continental Differences in Climate Asymmetrically Shape Temporal Ecological Processes in Riverine Insect Diversity - Xiaowei Lin; Qingyi Luo; Mei‐Hwa Kuo; Zihao Wen; Qinghua Cai; Ming‐Chih Chiu; Vincent H. Resh (Global Change Biology, 2026)
Climatic fluctuations can play a crucial role in shaping large‐scale patterns of biodiversity and biogeography. This study examines how climatic gradients and their variability influence family‐level temporal ecological processes that govern the balance between stochastic and deterministic processes that underlie community dynamics of riverine insects. This comparison, done across multiple continents but mostly in the Northern Hemisphere, used long‐term data from 302 sites mainly in Europe, ranging from 10 to 37 years, and with 4751 observations of family‐level riverine insect assemblages. We analyzed spatial patterns in family richness, family‐level temporal beta diversity, and associated ecological processes. Generalized additive models revealed high spatial heterogeneity, with family‐level richness declining with latitude, but total family‐level temporal beta‐diversity decreasing with increasing latitude and elevation across the continents studied. The cross‐continental results from generalized additive and dissimilarity models further showed spatial shifts in the proxy indicators of ecological processes (e.g., environmental variables and time‐series decomposition), with stochastic processes (e.g., ecological drift) increasing in importance towards higher latitudes. In contrast, deterministic processes (e.g., temperature) declined. At a cross‐continental perspective, these findings highlight how spatial asymmetry under fluctuating climates may shape riverine insect community dynamics and improve adaptive conservation strategies.

Experimentally derived buoyancy duration of seagrass fragments for biophysical dispersal modelling in the Great Barrier Reef - Douchan Hanuise; Chieh Lin; Samantha Tol; Severine Choukroun; Michael A. Rasheed; Thomas Dobbelaere; Paul H. York; Timothy M. Smith; Robert G. Coles; Emmanuel Hanert; Alana Grech (Marine Environmental Research, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Hybrid photocatalytic–microbial fuel cells systems: Progress, challenges, and forecasts in water-energy-environment nexus - Rabia Tasaduq Hussain; Baala H. Anandapadmanaban; Chi-Wen Lin; Shu-Hui Liu; Jun Haslinda Shariffuddin (Journal of Environmental Chemical Engineering, 2026)

Machine learning and spatial regression approaches to estimating willingness to pay for ecosystem services in Jakarta and Taoyuan - Shafira Wuryandani; Yu-Pin Lin; Pei-Chen Lin; Dirk S. Schmeller; Gerard H. Ros (Ecosystem Services, 2026)

Roof-integrated phase change materials for urban heat island mitigation: advances and strategies - H. Zhan; G. Lin (International Journal of Environmental Science and Technology, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Local reaction-global diffusion unlocks high-performance Mg3(Sb,Bi)2-based thermoelectrics - Zhen Fan; Yi Wang; Tenglong Lu; Xiaofan Zhang; Jiawei Yang; Kaiwei Guo; Joseph Woods; Gang Wang; Xiaoyan Niu; Qi Zhao; Xiaowei Wu; Fankai Xie; et al. (Science Bulletin, 2026)

Towards low-carbon construction: Nature-inspired internal patterns for thermal insulation in lightweight concrete component cast using 3D-printed formwork - Hanmo Wang; Yujia Wan; Shawn Owyong; En Tian Connie Lim; Abhimanyu Goel; Anqi Shi; Zhuyin Lu; Tam H Nguyen; Harn Wei Kua; Sunmi Shin; Alexander Lin (Energy and Buildings, 2026)

Identification of multiple galectins as receptors for β-1,3-glucans - Xuejiao Xu; Zhen He; Yuanning Wang; Xiushi Jia; Andong Zhou; Yibing Wang; Yitong Li; Jieyi Long; Kevin H. Mayo; Lin Sun; Yifa Zhou; Zihan Zhao; et al. (Carbohydrate Polymers, 2026)

Microfibril orientation and compositional heterogeneity in fiber and vessel cell walls of poplar xylem studied by AFM-IR and SFG spectroscopy - Jongcheol Lee; Juseok Choi; Yen-Ting Lin; Fangxin Qian; Botong Tong; Quanzi Li; Seong H. Kim (Planta, 2026)
Main conclusion This study demonstrates the use of photothermal AFM-IR and vibrational SFG microscopy to investigate nanoscale chemical heterogeneity and mesoscale cellulose microfibril orientation in hybrid poplar xylem, revealing differences in cellulose microfibril (CMF) orientation between fiber and vessel cell walls that are consistent with their mechanical support and hydraulic functions. Abstract Understanding the structural organization of cellulose microfibrils (CMFs) within individual plant cell walls is essential for connecting cell wall architecture to its mechanical and physiological functions. However, due to the complex hierarchical structure and nanoscale heterogeneity of cell walls, it remains technically challenging to resolve detailed compositional and orientational information at subcellular levels of individual cell walls. This study investigates the internal 3D structure, chemical composition, and sublayer organization of fiber and vessel cell walls in the xylem tissue of a two-year-old field-grown hybrid poplar tree ( Populus alba × P. glandulosa ) using photothermal atomic force microscopy coupled with infrared spectroscopy (AFM-IR) and sum frequency generation (SFG) hyperspectral microscopy. AFM-IR provided nanoscale chemical imaging, revealing localized compositional heterogeneity, including variations between adjacent cell walls and transitional layers beyond the traditional S1, S2, and S3 sublayers. SFG microscopy revealed that CMFs in fiber walls are highly aligned along the stem axis, consistent with their role in mechanical support, while vessel cell walls exhibited slightly tilted CMFs, reflecting their function in hydraulic transport. Together, these results offer new insights into cell-type-specific CMF organization and compositional gradients in hybrid poplar xylem. These findings highlight the structural and chemical complexity of secondary cell walls in woody plants and demonstrate the value of AFM-IR and SFG spectroscopy in elucidating plant cell wall architecture. Graphical abstract .

Prenatal exposure to extreme heat and autism in children - David G. Luglio; Xin Yu; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Nathan Pavlovic; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Artificial neural network modeling for adsorption processes in carbon capture from wet flue gas - H. Si; J.K. Wu; S. Chen; J.Y. Yong; X.J. Lin; M.X. Fang; L. Jiang (Gas Science and Engineering, 2026)

Tannase-catalysed gallic acid release for clean-label inhibition of green tea auto-oxidative browning - Junfeng Tan; Mark G. Sanders; Janniek H. Ritsema; Bram van de Put; Jean-Paul Vincken; Zhi Lin; Wouter J.C. de Bruijn (Food Chemistry, 2026)

Variable roles of oceanic transform faults in plume dispersion along segmented mid-ocean ridges - Fan Zhang; Sibiao Liu; Lars H. Rüpke; Yiming Luo; Ming Chen; Xubo Zhang; Lei Zhao; Yinuo Zhang; Zhanying Chen; Jian Lin (Earth and Planetary Science Letters, 2026)

Structural analysis and immunomodulatory properties of lipopolysaccharide from the gut symbiont Phocaeicola dorei - Zhiying Lin; Huazhi Tang; Limei Che; Mingsheng Chen; Zixin Ye; Xiaotong Yang; Lin Sun; Kevin H. Mayo; Guihua Tai; Liangnan Cui; Yifa Zhou (Carbohydrate Polymers, 2026)

Individual‐Level Trait Responses in Cyanobacterial Populations and Communities - Arnaud P. Louchart; Annemieke M. Drost; Chaohong Lin; Suzanne M. H. Naus‐Wiezer; Zhipeng Duan; Elena Litchman; Dedmer B. Van de Waal (Ecology Letters, 2026)
Trait‐based approaches support the mechanistic understanding of individual organism responses to resource availabilities that underlie population and community dynamics. For microbes such as phytoplankton, however, it remains challenging to obtain individual cell traits, particularly in natural communities. Here, we provide a flow cytometry‐based approach using a freshwater cyanobacterium Microcystis spp. culture and assessed individual‐level trait responses to nitrogen, phosphorus and light limitation and high p CO 2 . Then, these responses served as ‘fingerprints’ to describe the main drivers in natural cyanobacterial communities. We observed distinct responses in multidimensional trait space, that is, the integrated phenotype, which differed particularly between nitrogen and light limitation. Notably, cellular contents of the pigments phycocyanin and chlorophyll‐a decreased with nitrogen limitation and increased with light limitation, which was confirmed in natural communities. Overall, our results show how individual‐trait responses to known environmental conditions can be used to understand natural cyanobacterial population and community dynamics.

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

Dual-function microalgal microbial fuel cell for simultaneous wastewater remediation and bioelectricity generation under magnetically stirred cathode configuration - Chi-Wen Lin; Shu-Hui Liu; Yu-Shen Cheng; Baala H. Anandapadmanaban (Journal of Water Process Engineering, 2026)

Residence time distribution in flow reactors for solid phase synthesis - Sebastián Pinzón-López; Wei-Hsin Hsu; Dominik Ebert; Mei-Huei Lin; Matthias Kraume; Peter H. Seeberger; José Danglad-Flores (Chemical Engineering Journal, 2026)

Expansion of Molecular and Clinical Aspects of EPS8L2 (DFNB106)-Associated Hearing Loss Emphasizes a Potential Therapeutic Window - Daniel Owrang; Aboulfazl Rad; Masoome Alerasool; Susanne M. Kolb; Sheng-Jia Lin; Julia Doll; Neda Alidadiani; Shahrooz Ghaderi; Michaela A. H. Hofrichter; Reza Maroofian; Gaurav K. Varshney; Majid Mojarrad; et al. (Molecular Neurobiology, 2026)
EPS8L2, encoding EPS8 signaling adaptor L2 protein, is critical for stereocilia maintenance in cochlear hair cells. Four previously published families have replicated autosomal recessive non-syndromic hearing loss (DFNB106), yet the mutational and clinical spectrum remains poorly described. This study expands the mutational and clinical spectrum of EPS8L2 -associated hearing impairment by identifying five additional individuals in four families, more than doubling the number of reported cases to date, while going deeper into clinical aspects. These include two frameshift variants c.818_827dup, p.(Ala279Glyfs*36) and c.1430dup, p.(Val478Serfs*25), the first nonsense variant c.1878C > A, p.(Tyr626Ter), and the first missense variant with a spliceogenic effect c.767C > G, p.(Thr256Arg). Functional analysis confirmed that the c.767C > G variant causes exon 9 skipping, leading to a frameshift r.701_768del, p.(Gly234Alafs*55). A shared 4.17 Mb homozygous region among two unrelated Iranian families with this variant suggested a founder effect. These individuals uniquely showed U-shaped audiograms as a new association of more severe middle frequency hearing loss. Clinically, affected individuals presented moderate to moderately severe hearing loss that was mostly progressive, with an onset starting between the prelingual stage, extending postlingually. A younger sibling of the first European proband diagnosed with DFNB106 passed newborn hearing screening but was identified with compound heterozygous variants, underscoring the importance of early genetic testing. The progressive nature of EPS8L2 -related hearing loss is unusual for recessive non-syndromic forms and highlights the need for early monitoring and intervention. This work emphasizes the need for early molecular diagnosis and long-term clinical follow-up, while describing the natural history of EPS8L2 that will be important for future therapeutic development.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Preventing molecular catalyst aggregation in Z-scheme photocatalyst for unassisted CO2 reduction - Sharafat Ali; Sajjad Ali; Mohammad Z. Rahman; Lin Xu; Min Liu; Chuan Ke; Ahmed Ismail; Syedul H. Bakhtiar; Sher Ali; Muneerah Alomar; Zhenghua Wu; Li Zhong; et al. (Journal of Environmental Chemical Engineering, 2025)

Stabilization of nanoemulsions using cold-water fish gelatin and whey protein isolates/fibrils - Yichen Lin; Yrjö H. Roos; Maurice O'Sullivan; Song Miao (Food Hydrocolloids, 2025)

An effective ECG signal classification method based on a minimalistic memristive reservoir computing system - Xiaoyuan Wang; Meng Yang; Yuji Zeng; Zhuosheng Lin; Herbert H. C. Iu (Cognitive Neurodynamics, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Physics-Informed Graph Neural Networks: Predicting the composite mechanical behavior of clay-infilled concrete structures with morphed honeycomb configurations - Hanmo Wang; Febi Rhiana; Anqi Shi; Zhuyin Lu; Mingkai Li; Tao Wang; Tam H. Nguyen; Alexander Lin (Engineering Structures, 2025)

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

Association between blood nicotinamide adenine dinucleotide levels and blood laboratory parameters at baseline and after nicotinamide mononucleotide supplementation in middle-aged healthy individuals: post hoc analysis of a randomized, double-blinded, placebo-controlled clinical trial - Ajla H. Kuerec; Weilan Wang; Keona D. M. Fokke; Lin Yi; Zhigang Lin; Aditi Vaidya; Sohal Pendse; Sornaraja Thasma; Niranjan Andhalkar; Ganesh Avhad; Vidyadhar Kumbhar; Andrea B. Maier (GeroScience, 2025)

Circular economy models of sugarcane biorefinery towards carbon neutrality and environmental sustainability - Shwe Yie Lin; Nicholas M. Holden; Romanee Thongdara; Thapat Silalertruksa; Shabbir H. Gheewala; Trakarn Prapaspongsa (Sustainable Production and Consumption, 2025)

Mediating Pathways Between Food Insecurity and Later-age Sleep Quality - J. Wang; J. Luo; H. Lin; P. Quinn; A. Chow (Journal of the Academy of Nutrition and Dietetics, 2025)

A robust method for quantitative detection of β-1,3-glucan using Limulus polyphemus factor Gα fragment - Andong Zhou; Yitong Li; Yuanning Wang; Yibing Wang; Zhonghui Qiao; Kevin H. Mayo; Zihan Zhao; Lin Sun (Carbohydrate Polymers, 2025)

P09-29 Aflatoxin B1 exposure induces AD-like pathology through perturbation of redox homeostasis and activation of ferroptotic signalling in C57BL/6J mice - H. Hong; J. Lin; W. Yuan; Z. Zhou (Toxicology Letters, 2025)

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

A novel adsorbent for efficient metal recovery from aqueous solutions: Carbon-coated oil-treated plastic granules as a sustainable approach to resource conservation - Farideh Pahlavan; Harpreet Kaur; Hamed Khodadaditirkolaei; Sk Faisal Kabir; Jung-Ying Lin; Laura K. G. Ackerman-Biegasiewicz; Elham H. Fini (Resources, Conservation and Recycling, 2025)

Red mud amendments reduce cadmium mobility in paddy soil and limit cadmium accumulation in rice grains: A mechanistic investigation - Jiali Yan; Xuwei Li; Jintao Li; Jiankang Zhou; Jiamin Shi; Kangfu Liu; Xin Chen; Shiqi Zhou; Weiwei Sun; Fuqing Sui; Xiaochen Lin; Lei Zhang; et al. (Plant and Soil, 2025)

Adsorption of phosphorus on different substrates of constructed wetlands - X. Liu; M. Tang; C. Lin; H. Zhu; Z. Xu; H. Zhai; X. Tan (International Journal of Environmental Science and Technology, 2025)

Assessing the relationship between digital service trade and carbon emissions: evidence from RCEP countries - H. Liu; L. Liu; L. Lin (International Journal of Environmental Science and Technology, 2025)

Impact of U-10Mo HALEU fuel element tolerances on the Massachusetts Institute of Technology reactor safety and operational performance – Thermal hydraulics - Sero Yang; Valerio Mascolino; Laura M. Jamison; Kyle E. Anderson; Lin-wen Hu; Dhongik S. Yoon; John A. Stillman; Walid M. Mohamed; Erik H. Wilson (Annals of Nuclear Energy, 2025)

Impact of U-10Mo HALEU Fuel Element Tolerances on the Massachusetts Institute of Technology Reactor safety and operational performance – Neutronics - Valerio Mascolino; Sero Yang; Laura M. Jamison; Kyle E. Anderson; Lin-wen Hu; Dhongik S. Yoon; John A. Stillman; Walid Mohamed; Erik H. Wilson (Annals of Nuclear Energy, 2025)

Museomics and Salvaged Feathers Piece Together the Evolutionary History and Conservation Genomics of the Elusive, Critically Endangered Night Parrot ( Pezoporus occidentalis ) - Heng Lin Yeap; Gunjan Pandey; Jeremy J. Austin; John G. Oakeshott; Christopher M. Hardy; Stephen A. Murphy; Nicholas P. Leseberg; Allan H. Burbidge; Kenny J. Travouillon; Leo Joseph; Anna M. Kearns (Molecular Ecology, 2025)
The Night Parrot is a critically endangered nocturnal bird of Australia's arid zone. The species was “lost” for most of the 20th century until its rediscovery in 1990. Extant populations are now known in eastern and western Australia, but the species has been extirpated from much of its historical range. Here we estimate critically needed Essential Biodiversity Variables (EBVs) for the Night Parrot from historical and opportunistically collected contemporary samples. We find little population structure across the species' range and evidence of recent connectivity between extant populations ~2000 km apart. Most eastern individuals show significant kinship with one another, as did two from an extinct population in southern Australia. Heterozygosity is similarly low in all extant populations but ten‐fold lower in the extinct population sampled. Coalescent modelling of effective population size ( Ne ) suggests that Night Parrot numbers were reasonably high until around 90 years ago when Ne crashed from ~10,000 to ~100. Current Ne is now at its lowest in the past several million years. Our findings will help guide the ongoing management of one of Australia's most threatened birds.

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

Collection, Characterization, and Diversity Analysis of New Wild Sugarcane Germplasm from Southeastern Yunnan Province, China - Chaohua Xu; Xuekuan Chen; Fenggang Zan; Peifang Zhao; Wei Qin; Chunyan Tian; Xiuqin Lin; Chunyan Kong; Hongbo Liu; Tanweer Kumar; Faisal Mehdi; Mahmoud H. M. Ebid; et al. (Sugar Tech, 2025)

Status quo and predictions of the most and least discussed sustainable development goals - H.-H. Chung; F.-L. Chung; S.-M. Lin (International Journal of Environmental Science and Technology, 2025)

Comparison of indoor hydroponic plants for decarbonization and cooling performance: the field experiment of three vegetation species - G. Zhang; Q. Lin; X. Li; H. Xia; H. Li (International Journal of Environmental Science and Technology, 2025)

Intact reinforcement learning in healthy ageing - Wei-Hsiang Lin; Karin S. Pilz; Michael H. Herzog; Marina Kunchulia (Experimental Brain Research, 2025)
What changes with age? Results in reinforcement learning (RL) are mixed. Some studies found deteriorated RL performance in older participants compared to younger controls whereas other studies did not. Daniel et al. (J Neurosci 40(5):1084–1096, 2020. 10.1523/JNEUROSCI.0254-19.2019) suggested that task demand can explain these differences, with less demanding tasks showing no effect of age. Compared to classic, simple RL tasks, we used a navigation task to increase overall complexity. We found that older adults performed less efficiently initially; however, with sufficient trials, they performed as well as young adults. Our results support the idea that ageing does not universally impair performance and that even higher-level cognitive tasks remain largely intact.

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Conformational and rheological property comparison for three exudates gums containing type II arabinogalactans - Xing Jia; Zhiyuan Xu; Meng Xiao; Yueru Jiang; Lin Ma; Wan Wang; Qiaomei Zhu; Ji Kang; Qingbin Guo; H. Douglas Goff (Food Hydrocolloids, 2025)

Effect of honeycomb core cell geometry on the sandwich tube for internal blast loading - Vuong Nguyen-Van; Ngoc San Ha; H. Nguyen-Xuan; Xiaoshan Lin; Yi Min Xie; Guoxing Lu (Engineering Structures, 2025)

Discordant sibling analysis of autism risk associated with prenatal exposure to tailpipe and non-tailpipe particulate matter pollution - Anny H. Xiang; Jane C. Lin; Ting Chow; Xin Yu; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Michael J. Kleeman; Rob McConnell; Md. Mostafijur Rahman (Environmental Research, 2025)

Influence of infant feeding practices on childhood dietary patterns in Upstate KIDS - Priscilla K. Clayton; Diane L. Putnick; Tzu-Chun Lin; Edwina H. Yeung (Appetite, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Boosting photocatalytic H2O2 production and non-biodegradable ofloxacin removal via a novel Ti3C2 MXene nanosheet-supported BiVO4/InVO4 Z-scheme heterojunction: Optimization and mechanism insights - Jun Zhao; Ali B.M. Ali; Abdul Amir H. Kadhum; Haitao Lin; Ali Saber Abdelhameed; Amer M. Alanazi; Ibrahim Mahariq; Egambergan Khudoynazarov; Doniyor Jumanazarov; Farruh Atamurotov (Journal of Water Process Engineering, 2025)

3D printing fortified pea-based snacks with precise vitamin dosing by binder jetting - Ethan Chadwick; Guilherme P.S.R. Bertola; Xinhao Lin; Ann H. Barrett; Michael Okamoto; Xiuling Lu; Anson W.K. Ma (Journal of Food Engineering, 2025)

Transglutaminase crosslinked fish gelatin emulsion gels: Structure, rheology behaviors, and delivery functionality - Yichen Lin; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Optimizing the generated waste proportion to improve the characteristics of biochar for CO2 sequestration and other applications - Baala H. Anandapadmanaban; Yen San Chan; Chi-Wen Lin; Shu-Hui Liu (Environment, Development and Sustainability, 2025)

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

Life cycle assessment of the thermal oxidation and pyrolysis of granular activated carbon loaded with perfluorooctane sulfonic acid (PFOS) - Zunhui Lin; Kyle Doudrick; Pierre Herckes; Mikhail Chester; Paul Westerhoff; Treavor H. Boyer (Journal of Cleaner Production, 2025)

Landsat 8 OLI atmospheric correction neural network for inland waters in tropical regions - M. Van Nguyen; O. T. La; H. T. T. Nguyen; D. Heriza; B.-Y. Lin; G. Y. I. Ryadi; Chao-Hung Lin; Vinh Quang Pham (International Journal of Environmental Science and Technology, 2025)

Collection of stomatopod larvae unveiled the existence of an undescribed genus in Lysiosquillidae around Japanese waters - Koshi Fujita; Chia-Wei Lin; Kingsley J. H. Wong; Mikio Kato; Tin-Yam Chan; Kaori Wakabayashi (Marine Biodiversity, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Bayesian enhanced graph neural networks: Refining design spaces for hollow concrete components with optimum mechanical performance - Alexander Lin; Hanmo Wang; Wei He; Shawn Owyong; Huan Ting Chen; Tam H. Nguyen (Engineering Structures, 2025)

Prospects of microalgae in the cathode chamber of microbial fuel cells: From sequestration to bioproduct production - Baala H. Anandapadmanaban; Shu-Hui Liu; Chi-Wen Lin (Biomass and Bioenergy, 2025)

Cubic calcite and its structural phase transitions - Yang Yang; Yixin Lin; Xiangdong Ding; Christopher J. Howard; Ekhard K. H. Salje (Physics and Chemistry of Minerals, 2025)
Calcite, CaCO 3 , has been reported to exist in as many as seven different structural forms. The structure at room temperature and pressure (space group R $$\overline{3 }$$ 3 ¯ c , ‘Phase I’) was established by Bragg many years ago. A phase transition to a higher temperature phase (space group R $$\overline{3 }$$ 3 ¯ m, ‘Phase V’) was noted to occur at around 1240 K—this may proceed via an intermediate phase (space group again R $$\overline{3 }$$ 3 ¯ c , referred to as ‘Phase IV’). These phases differ primarily in the disposition of the CO 3 groups. Additional phases are found at higher pressures. We report a para-phase (parent phase, virtual prototype, aristotype) which assists in understanding the different phases, the phase transitions, and especially the domain structures and twin wall boundaries associated with these transitions. Molecular dynamics methods were used to study the temperature evolution of an isothermal-isobaric (NPT) ensemble of some 384,000 atoms. These computations reproduced the features of the known structures in R $$\overline{3 }$$ 3 ¯ c and R $$\overline{3 }$$ 3 ¯ m and then, at higher temperature, revealed a structure of the sodium chloride type (space group Fm $$\overline{3 }$$ 3 ¯ m ) in which the entities were the Ca 2+ cation and the CO 3 2− anion, this latter with effectively spherical symmetry. On this basis we have upon cooling a necessarily first order ferroelastic transition from cubic Fm $$\overline{3 }$$ 3 ¯ m to rhombohedral R $$\overline{3 }$$ 3 ¯ m , computed to occur at a simulated temperature of 1900 K, and a possibly continuous transition from the R $$\overline{3 }$$ 3 ¯ m to rhombohedral (on a doubled cell) R $$\overline{3 }$$ 3 ¯ c computed to occur at about 1525 K. The computations also allowed us to follow the domain structure and twin walls as a function of temperature, during both heating and cooling. The structure just below the R $$\overline{3 }$$ 3 ¯ m to R $$\overline{3 }$$ 3 ¯ c transition shows strong disorder in the orientation of the CO 3 groups, and this may be what is sometimes referred to as Phase IV. The domain structure just below the cubic to rhombohedral transition shows twinning of typical ferroelastic character. The doubling of the cell below the R $$\overline{3 }$$ 3 ¯ m to rhombohedral (on a doubled cell) R $$\overline{3 }$$ 3 ¯ c leads to a more complicated twin pattern. Indeed, the different structures can be identified from patterns of twinning. Differences between domain structures obtained on heating and cooling indicate extensive thermal metastabilities.

Downregulation of A20 Expression Related to T Cells by Staphylococcal Enterotoxin A Treatment - X. Chen; Y. Yan; C. Lin; J. Yang; H. Qiu (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The effect of whey/soy protein fibril systems on the properties of fish gelatin stabilized emulsion gels - Yichen Lin; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2025)

Acoustic insulation optimization of walls and panels with functional graded hollow sections using graph transformer evaluator and probability-informed genetic algorithm - Hanmo Wang; Tam H Nguyen; Zhuyin Lu; Febi Rhiana; Dickson Fong; Wei He; Shawn Owyong; Huan Ting Chen; Alexander Lin (Building and Environment, 2025)

Epigenetic modifications control CYP1A1 Inducibility in human and rat keratinocytes - Lo-Wei Lin; Allison K. Ehrlich; Robert H. Rice (Toxicology and Applied Pharmacology, 2025)

Evaluation of sustainable waste management: An analysis of techno-economic and life cycle assessments of municipal solid waste sorting and decontamination - Maria A. Herrera Diaz; Yingqian Lin; Pralhad H. Burli; Tasmin Hossain; Damon S. Hartley; Vicki S. Thompson (Resources, Conservation and Recycling, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Recovery of terephthalic acid from alkali-decrement wastewater by zinc salt-based coagulation - H. Zhu; C. Guo; C. Xu; Y. He; M. Huang; G. Zhou; Y. Lin (International Journal of Environmental Science and Technology, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Decomposing the variance: The unique and shared associations of fine and ultrafine particulate matter exposed during pregnancy with child autism spectrum disorder - Xin Yu; Michael J. Kleeman; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Jiu-Chiuan Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2024)

Life history traits and abundance trends of emperor fish Lethrinus nebulosus and L. lentjan (Teleostei: Lethrinidae) in the western Arabian Gulf - Yu-Jia Lin; Premlal Panickan; Abdu Rahiman Kambrath Pulikkoden; Nabil Fita; Ali M. Qasem; Lotfi J. Rabaoui; Ruben H. Roa-Ureta; Mohammad A. Qurban (Regional Studies in Marine Science, 2024)

A modified self-micro emulsifying liposome for bioavailability enhancement of quercetin and its biological effects - S.Y. Lin; T.T. Chen; Mohamed A. Farag; H. Teng; H. Cao (Food Bioscience, 2024)

Effects of the organochlorine pesticide metabolite p,p’-DDE on the gastrointestinal lipidome in fish: A novel toxicity pathway for a legacy pollutant - Alexis M. Wormington; David J. Gabrielli; Mohammad-Zaman Nouri; Ashley M. Lin; Sarah E. Robinson; John A. Bowden; Nancy D. Denslow; Tara Sabo-Attwood; Joseph H. Bisesi (Environmental Pollution, 2024)

Application of an α-galactosidase from Bacteroides fragilis on structural analysis of raffinose family oligosaccharides - Heyang Zu; Xuecui Yan; Jing Wu; Jingying Zhao; Kevin H. Mayo; Yifa Zhou; Liangnan Cui; Hairong Cheng; Lin Sun (Carbohydrate Polymers, 2024)

Oligosaccharides from Stellaria dichotoma L. var. lanceolate bind to galectin-3 and ameliorate effects of colitis - Zihan Zhao; Jing Wu; Xuejiao Xu; Zhen He; Xiang Wang; Jiyong Su; Kevin H. Mayo; Lin Sun; Liangnan Cui; Yifa Zhou (Carbohydrate Polymers, 2024)

Construction and Behavioral Comparison of Two Mouse Models of Cerebral Palsy - Y. Tang; Y. Li; S. Lin; W. Wei; H. Chen (Bulletin of Experimental Biology and Medicine, 2024)

Outdoor physical activity is not associated with better mental health in a sample of predominantly Black people, but spending time in parks is - Amber L. Pearson; Wei Liu; Zihan Lin; Teresa H. Horton; Jennifer D. Roberts; Tim Chambers; Ashton Shortridge; Karin A. Pfeiffer; Joseph Gardiner (Urban Forestry & Urban Greening, 2024)

Spatial asymmetry of temporal ecological processes can shift in riverine macroinvertebrates responding to fluctuating climate conditions - Xiaowei Lin; Zhen Tian; Qingyi Luo; Jingting Li; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Science of The Total Environment, 2024)

Colloidal and interfacial properties of spray dried pulse protein-blueberry polyphenol particles in model dispersion systems - Yufeng Lin; Nicholas Cheng; Yueyue Jiang; Mary H. Grace; Mary Ann Lila; Roberta Targino Hoskin; Haotian Zheng (Food Chemistry, 2024)

Impact of cross-reactivity and herd immunity on SARS-CoV-2 pandemic severity - Nana Owusu-Boaitey; Lucas Böttcher; Daihai He; Ryenchindorj Erkhembayar; Lin Yang; Dong-Hyun Kim; Anton Barchuk; David H. Gorski; Jonathan Howard (Infectious Diseases, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Molecular features of uranium-binding natural organic matter in a riparian wetland determined by ultrahigh resolution mass spectrometry - Chen Xu; Aleksandar I. Goranov; Daniel I. Kaplan; Peng Lin; Chris M. Yeager; Nicole Patterson; Helen Jiang; Patrick G. Hatcher; Peter H. Santschi (Science of The Total Environment, 2024)

Speciation, phytoavailability, and accumulation of toxic elements and sulfur by humic acid-fertilized lemongrass and common sage in a sandy soil treated with heavy oil fly ash: A trial for management of power stations wastes - Samir G. Al-Solaimani; Abdulrahman Al-Qureshi; Sherif S. Hindi; Omer H. Ibrahim; Magdi A.A. Mousa; Yen-Lin Cho; Noha E.E. Hassan; Yu-Ting Liu; Shan-Li Wang; Vasileios Antoniadis; Jörg Rinklebe; Sabry M. Shaheen (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

Hydrological controls of a riparian wetland based on stable isotope data and model simulations - Peter H. Santschi; Chen Xu; Peng Lin; Chris M. Yeager; Pieter Hazenberg; Daniel I. Kaplan (Isotopes in Environmental and Health Studies, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Towards calorie-adequate diets to mitigate environmental impacts from food consumption in Asia - Shwe Yie Lin; Hnin Nandar Khine; Aakriti Deuja; Romanee Thongdara; Nawatch Surinkul; Nicholas M. Holden; Shabbir H. Gheewala; Trakarn Prapaspongsa (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Effects of stepwise depressurisation rate on methane hydrate dissociation dynamics at pore scale using microfluidic experiments - Junyu Yang; Qianghui Xu; Boyu Huang; Yizhe Liu; Zhiying Liu; Le Zhang; Kai H. Luo; Lin Shi (Gas Science and Engineering, 2024)

Spray combustion characteristics and soot formation potential of Nano-Al2O3 diesel at low ambient temperatures - Zhefeng Guo; Che-Wei Wu; Yee-Lin Wu; Yen-Yi Lee; Sheng-Lun Lin; Timothy H. Lee (Fuel, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Nonlinear contributions of surface solar brightening to maize yield gains in the US Corn Belt - H. Zhao; H. Yang; T.J. Avenson; G.F. Sassenrath; MB. Kirkham; S.W. Welch; L. Zhang; N. Wan; A.M. Nelson; P. Gowda; X. Lin (Agricultural and Forest Meteorology, 2024)

Correction to: Gas6 Promotes Microglia Efferocytosis and Suppresses Inflammation Through Activating Axl/Rac1 Signaling in Subarachnoid Hemorrhage Mice - Junjia Tang; Yichao Jin; Feng Jia; Tao Lv; Anatol Manaenko; Lin‑Feng Zhang; Zeyu Zhang; Xin Qi; Yajun Xue; Bin Zhao; Xiaohua Zhang; John H. Zhang; et al. (Translational Stroke Research, 2024)

Uranium-series and strontium isotope systematics in soil carbonates from dryland Critical Zones: Implications for soil inorganic carbon storage and transformation - Syprose K. Nyachoti; Victor H. Garcia; Curtis Monger; Craig Tweedie; Thomas E. Gill; Lixin Jin; Lin Ma (Geochimica et Cosmochimica Acta, 2024)

Pore-scale visualization of hydrate dissociation and mass transfer during depressurization using microfluidic experiments - Junyu Yang; Yizhe Liu; Qianghui Xu; Zhiying Liu; Xiaoye Dai; Lin Shi; Kai H. Luo (Fuel, 2024)

Preparation and identification of galacto-mannooligosaccharides generated from guar gum by a recombinant β-mannanase from Bacteroides fragilis (BF0736) - Xiang Wang; Xuecui Yan; Yaoqi Liu; Zhicong Song; Kevin H. Mayo; Lin Sun; Liangnan Cui; Yifa Zhou (Food Hydrocolloids, 2024)

Potential application of Ginkgo biloba extract as a green corrosion inhibitor for carbon steel reinforcement in chloride-polluted simulated concrete pore solution - Ambrish Singh; K.R. Ansari; Siham K. AbdelRahim; Ismat H. Ali; Brahim EL Ibrahimi; Abdullah K. Alanazi; Muhammad Younas; Yuanhua Lin (Process Safety and Environmental Protection, 2024)

Effects on soil carbon storage from municipal biosolids application to agricultural fields - Zheya Lin; G.W. Price; Chang Liang; David L. Burton; Derek H. Lynch (Journal of Environmental Management, 2024)

Liquid Na-K alloy is not viable anode material for High-Performance Na-Ion batteries - Hyeongjun Koh; Mohamed H. Hassan; Stella Lin; Lin Wang; Eric A. Stach; Eric Detsi (Chemical Engineering Journal, 2024)

Future changes in intense tropical cyclone hazards in the Pearl River Delta region: an air-wave-ocean coupled model study - Zhenning Li; Jimmy C. H. Fung; Mau Fung Wong; Shangfei Lin; Fenying Cai; Wenfeng Lai; Alexis K. H. Lau (Natural Hazards, 2024)
The Pearl River Delta (PRD) region is highly vulnerable to tropical cyclone (TC)-caused coastal hazards due to its long and meandering shoreline and well-developed economy. With global warming expected to continue or worsen in the rest of the twenty-first century, this study examines the TC impact on the PRD coastal regions by reproducing three intense landfalling TCs, namely Vicente (2012), Hato (2017), Mangkhut (2018), using a sophisticated air-wave-ocean coupled model of high spatial resolution (1-km atmosphere and 500-m wave and ocean). The simulations are conducted using present-day reanalysis data and the same TCs occurring in a pseudo-global warming scenario projected for the 2090s. Results indicate that the coupled model accurately reproduces the air-wave-ocean status during the TC episodes. The 2090s thermodynamic status effectively increases the intensity of intense TCs, leading to more severe coastal hazards including gale, rainstorm, and storm surges and waves. On average, the maximum surface wind speed within 50–200 km to the right of the TC center can increase by 4.3 m/s (+22%). The 99th and the 99.9th percentile of accumulated rainfall will increase from 405 to 475 mm (+17.3%), and from 619 to 735 mm (+18.6%), respectively. The maximum significant wave height at the ocean is lifted by an average of 57 cm (+13.8%), and the coastline typically faces a 40–80 cm increase. The maximum storm surges are lifted by 30–80 cm over the open sea but aggravate much higher along the coastline, especially for narrowing estuaries. For Typhoon Vicente (2012), there is more than a 200 cm wave height increase observed both at open sea and along the coastline. In the 2090s context, a combination of mean sea level rise, storm surge, and wave height can reach more than 300 cm increase in total water level at certain hot-spot coastlines, without considering the superposition of spring tides.

Concurrent Assessment on Blood Lead in Young Children and Toy Lead in Shanghai - Jiayu Peng; Zhenyan Gao; Jian Xu; Yanfen Lin; Aaron J. Specht; Shuwen Chen; Linda H. Nie; Linhua Huang; Chonghuai Yan (Exposure and Health, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Meteotsunamis in the Tamsui River estuary, Taiwan - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Estuarine, Coastal and Shelf Science, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Telomere dynamics during hibernation in a tropical primate - M. B. Blanco; D. L. Smith; L. K. Greene; A. D. Yoder; E. E. Ehmke; J. Lin; P. H. Klopfer (Journal of Comparative Physiology B, 2024)

Halorubrum hochsteinianum sp. nov., an ancient haloarchaeon from a natural experiment - Russell H. Vreeland; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Variability and distribution of nighttime equatorial to mid latitude ionospheric irregularities and vertical plasma drift observed by FORMOSAT-5 Advanced Ionospheric Probe in-situ measurements from 2017 – 2020 - Loren C. Chang; Yueh-Chun Hsieh; Chi-Kuang Chao; Yi Duann; Cornelius Csar Jude H. Salinas; Jann-Yenq Liu; Charles C.H. Lin (Advances in Space Research, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Advancing ecological assessment of the Arabian Gulf through eDNA metabarcoding: opportunities, prospects, and challenges - Thadickal V. Joydas; Seerangan Manokaran; Jayanath Gopi; Jayachandran P. Rajakumar; Lin Yu-Jia; Moritz Heinle; Mazen K. Nazal; Karuppasamy P. Manikandan; Maryam Qashqari; Sowmya P. Mohandas; Syed A. Hussain; Rommel H. Maneja; et al. (Frontiers in Marine Science, 2024)
The Arabian Gulf (hereafter ‘the Gulf’) is renowned for its unique ecological characteristics and distinct marine life. It offers a diverse range of ecosystems that have adapted to the impacts posed by natural stress and human activities. Regular biomonitoring and diversity assessments are necessary to document the health of the Gulf ecosystem and to implement appropriate measures for effective conservation and management. Recently, environmental DNA (eDNA), a total pool of DNA isolated from environmental samples, has emerged as a highly effective tool for ecological studies. This review explores the opportunities, prospects, and challenges associated with employing eDNA metabarcoding in the ecological assessment and biomonitoring of the Gulf. It provides an overview of the status of the Gulf ecosystem and discusses the potential applications of eDNA metabarcoding in assessing biodiversity, monitoring invasive species, and evaluating ecosystem health. Additionally, the investigation addresses the challenges inherent in implementing this technique, considering environmental complexities, methodological intricacies, and data interpretation. Overall, this review emphasizes the immense potential of eDNA metabarcoding in advancing ecological assessment in the Gulf and calls for further research and collaboration to harness its benefits in this unique marine ecosystem.

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Single-cell lineage tracing with endogenous markers - Yan Xue; Zezhuo Su; Xinyi Lin; Mun Kay Ho; Ken H. O. Yu (Biophysical Reviews, 2024)
Resolving lineage relationships between cells in an organism provides key insights into the fate of individual cells and drives a fundamental understanding of the process of development and disease. A recent rapid increase in experimental and computational advances for detecting naturally occurring somatic nuclear and mitochondrial mutation at single-cell resolution has expanded lineage tracing from model organisms to humans. This review discusses the advantages and challenges of experimental and computational techniques for cell lineage tracing using somatic mutation as endogenous DNA barcodes to decipher the relationships between cells during development and tumour evolution. We outlook the advantages of spatial clonal evolution analysis and single-cell lineage tracing using endogenous genetic markers.

A 16-year meteotsunami climatology in the coastal areas of southern Asia-Pacific Ocean - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Frontiers in Marine Science, 2024)
This study presents the meteotsunami behavior in response to different storm types in the coasts of southern Asia-Pacific Ocean from 16 years water level records. Through the size- frequency analysis, the dangerous meteotsunami, wave height exceeding 0.3 m, can occur up to 44 events per year. Notably, during the extreme waves of the 2007 event, wave heights reached approximately 0.9-1.5 m in the Taiwan Strait and the western coastal areas of Taiwan. We have classified storms into six types by radar reflectivity images and satellite-derived precipitation. Findings indicate that predicted wave heights caused by bows and typhoons could reach hazardous magnitude of exceeding 2 m in a 100-yr interval. Spatial and temporal analysis reveals that meteotsunami occurrences are most frequent in the western regions during the winter to early spring months (December to April). Of all meteotsunami occurrences, cluster storms are identified as the most prevalent atmospheric forcing, accounting for 60% of meteostunamis. Typhoons have a 20% association with meteotsunamis along the east coasts of Taiwan during late summer to autumn. On the east coasts, typhoon type-induced events may be attributed to the combination effect of meteotsunamis and infra-gravity waves. Overall, this study provides the first comprehensive examination of meteotsunami-storm characteristics and their associated hazard risks in the coastal areas of the southern Asia-Pacific Ocean.

Treatment of Moderate-to-Severe Glabellar Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-1 Phase 3 Trial - Nowell Solish; Amir Moradi; Sachin Shridharani; Lisa Donofrio; Michael H Gold; Brian Biesman; Melissa Chiang; Rosalyn George; Kristel Polder; Rob Schwarcz; Xiaoming Lin; Sarah Coquis-Knezek (Toxicon, 2024)

Exploring the therapeutic potential of layered double hydroxides and transition metal dichalcogenides through the convergence of rheumatology and nanotechnology using generative adversarial network - Suxian Lin; Weiwei Chen; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Yisu Ge; Yanjie Lu; Guodao Zhang; Mudan Wang (Environmental Research, 2024)

40 years of theoretical advances in mass-independent oxygen isotope effects and applications in atmospheric chemistry: A critical review and perspectives - Mang Lin; Mark H. Thiemens (Applied Geochemistry, 2024)

Aquaculture in Zambia: The Current Status, Challenges, Opportunities and Adaptable Lessons Learnt from China - Lin Zhang; Sahya Maulu; Fenglei Hua; Majory K. H. Chama; Pao Xu (Fishes, 2023)
As a land-locked country in Southern Africa, Zambia is rich in natural resources suitable for fish production. However, aquaculture is still in its infancy with enormous potential as most of Zambia’s fish now comes from capture fisheries. The aim of this study was to review the recent progress, status, challenges, and opportunities in Zambia’s aquaculture industry while drawing some lessons from China’s aquaculture experience, focusing on policy instruments, external support, quality seeds, and the investment environment for possible adaptation. To achieve this, we reviewed the existing literature about aquaculture in Zambia. This paper starts by reviewing the overall fishery sector’s developments based on the analysis of relevant statistics over decades before narrowing down to the aquaculture sub-sector. The review shows that aquaculture production has continued to expand significantly and will soon play a leading role in food and nutrition security in Zambia. However, the industry still faces major challenges relating to investments, science and technology, fish seed and feed, and an underdeveloped value chain besides the increasing demand for fish products. Nevertheless, great potential still exists to further develop the aquaculture sub-sector and meet the ever-growing demand for fish products caused mainly by the rapid population increase.

Radiometric assessment of OLCI, VIIRS, and MODIS using fiducial reference measurements along the Atlantic Meridional Transect - Silvia Pardo; Gavin H. Tilstone; Robert J.W. Brewin; Giorgio Dall'Olmo; Junfang Lin; Francesco Nencioli; Hayley Evers-King; Tânia G.D. Casal; Craig J. Donlon (Remote Sensing of Environment, 2023)

Clean and sustainable power/fresh water/hot air production scheme based on solid oxide fuel cell feed by apricot stone biomass: A multi-attribute optimization - Zhongjie Fei; Su Zhanguo; N.Bharath Kumar; Pradeep Kumar Singh; Zainab A. Farhan; Mahidzal Dahari; Haitao Lin; H. Elhosiny Ali; Souhail Mohamed Bouzgarrou (Process Safety and Environmental Protection, 2023)

Identification of a fundamental cryoinjury mechanism in MSCs and its mitigation through cell-cycle synchronization prior to freezing - Brian H. Johnstone; Dongsheng Gu; Chieh-Han Lin; Jianguang Du; Erik J. Woods (Cryobiology, 2023)

Gas6 Promotes Microglia Efferocytosis and Suppresses Inflammation Through Activating Axl/Rac1 Signaling in Subarachnoid Hemorrhage Mice - Junjia Tang; Yichao Jin; Feng Jia; Tao Lv; Anatol Manaenko; Lin-Feng Zhang; Zeyu Zhang; Xin Qi; Yajun Xue; Bin Zhao; Xiaohua Zhang; John H. Zhang; et al. (Translational Stroke Research, 2023)

Peripheral MC1R Activation Modulates Immune Responses and is Neuroprotective in a Mouse Model of Parkinson’s Disease - Pranay Srivastava; Shuhei Nishiyama; Fang Zhou; Sonia H. Lin; Akriti Srivastava; Chienwen Su; Yuehang Xu; Weiyi Peng; Michael Levy; Michael Schwarzschild; Xiqun Chen (Journal of Neuroimmune Pharmacology, 2023)
Background Melanocortin 1 receptor ( MC1R ) is a key pigmentation gene, and loss-of-function of MC1R variants that produce red hair may be associated with Parkinson’s disease (PD). We previously reported compromised dopaminergic neuron survival in Mc1r mutant mice and dopaminergic neuroprotective effects of local injection of a MC1R agonist to the brain or a systemically administered MC1R agonist with appreciable central nervous system (CNS) permeability. Beyond melanocytes and dopaminergic neurons, MC1R is expressed in other peripheral tissues and cell types, including immune cells. The present study investigates the impact of NDP-MSH, a synthetic melanocortin receptor (MCR) agonist that does not cross BBB, on the immune system and the nigrostriatal dopaminergic system in mouse model of PD. Methods C57BL/6 mice were treated systemically with MPTP.HCl (20 mg/kg) and LPS (1 mg/kg) from day 1 to day 4 and NDP-MSH (400 µg/kg) or vehicle from day 1 to day 12 following which the mice were sacrificed. Peripheral and CNS immune cells were phenotyped and inflammatory markers were measured. The nigrostriatal dopaminergic system was assessed behaviorally, chemically, immunologically, and pathologically. To understand the role of regulatory T cells (Tregs) in this model, CD25 monoclonal antibody was used to deplete CD25 + Tregs. Results Systemic NDP-MSH administration significantly attenuated striatal dopamine depletion and nigral dopaminergic neuron loss induced by MPTP + LPS. It improved the behavioral outcomes in the pole test. Mc1r mutant mice injected with NDP-MSH in the MPTP and LPS paradigm showed no changes in striatal dopamine levels suggesting that the NDP-MSH acts through the MC1R pathway. Although no NDP-MSH was detected in the brain, peripheral, NDP-MSH attenuated neuroinflammation as observed by diminished microglial activation in the nigral region, along with reduced TNF-α and IL1β levels in the ventral midbrain. Depletion of Tregs was associated with diminished neuroprotective effects of NDP-MSH. Conclusions Our study demonstrates that peripherally acting NDP-MSH confers protection on dopaminergic nigrostriatal neurons and reduces hyperactivated microglia. NDP-MSH modulates peripheral immune responses, and Tregs may be involved in the neuroprotective effect of NDP-MSH.

Effects of phosphorus supply and salt stress on plant growth, organic acid concentration, and sodium, potassium, calcium, magnesium, and phosphorus utilization in wheat - De-Yong Zhao; Zai-Wang Zhang; Guo-Lan Liu; Shuai-Peng Zhao; Xiao-Lin Zhang; Wang-Feng Zhao; Kadambot H. M. Siddique (Cereal Research Communications, 2023)

Challenging Dietary Research Measures, Concepts, and Definitions to Promote Greater Inclusivity of Immigrant Experiences: Considerations and Practical Recommendations - Shahmir H. Ali; Nelson F. Lin; Stella S. Yi (Journal of the Academy of Nutrition and Dietetics, 2023)

A state-of-the-art analysis of pharmacological delivery and artificial intelligence techniques for inner ear disease treatment - Wanqing Li; Nan Zheng; Qiang Zhou; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Huajun Zhao; Sen Lin (Environmental Research, 2023)

Retention and transport of PFOA and its fluorinated substitute, GenX, through water-saturated soil columns - Guanhong Liu; Muhammad Usman; Tao Luo; Pierre-François Biard; Kuangfei Lin; H. Chris Greenwell; Khalil Hanna (Environmental Pollution, 2023)

The effect of polychlorinated biphenyls extracted from offshore sediments on the intestinal epithelium and microflora of zebrafish - M. Zhang; D-H Zhu; Q-L Song; M-M Chen; Y Hu; D-J Kang; Z-B Chen; H-Y Lin; F-H Nie; J-J Chen (International Journal of Environmental Science and Technology, 2023)

Biosimilars approvals by thirteen regulatory authorities: A cross-national comparison - Fernanda Lacerda da Silva Machado; Martín Cañás; Svetlana V. Doubova; Martín A. Urtasun; Gustavo H. Marín; Claudia Garcia Serpa Osorio-de-Castro; Flavia Caixeta Albuquerque; Tatiane Bonfim Ribeiro; Lisa Pont; José Crisóstomo Landeros; Juan Roldán Saelzer; Dino Sepúlveda Viveros; et al. (Regulatory Toxicology and Pharmacology, 2023)

Uncovering the prevalence and drivers of antibiotic resistance genes in soils across different land-use types - Jie Wu; Shumin Guo; Haiyan Lin; Kejie Li; Zhutao Li; Jinyang Wang; William H. Gaze; Jianwen Zou (Journal of Environmental Management, 2023)

Unique hierarchical structures of one dimensional lepidocrocite titanate with cation-exchangeable sites for extraordinary selective actinide capture for water purification - Lin Wang; Hussein O. Badr; Yang Yang; Jacob H. Cope; Enzhao Ma; Jiafeng Ouyang; Liyong Yuan; Zijie Li; Zhirong Liu; Michel W. Barsoum; Weiqun Shi (Chemical Engineering Journal, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Characterization of fouled ultrafiltration membranes from a full-scale wastewater reclamation plant in iron and steel industry - P.-H. Lin; Y.-C. Su; C.-L. Chen; I.-Y. Tsao (International Journal of Environmental Science and Technology, 2023)

The impact of education level on residents’ carbon consumption in China - Y.-N. Lin; Y.-H. Chiu; T.-H. Chang; T.-Y. Lin; S.-Y. Chiu (International Journal of Environmental Science and Technology, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Elastic scattering dominates high-frequency seismic attenuation in Southern California - Yu-Pin Lin; Thomas H. Jordan (Earth and Planetary Science Letters, 2023)

The model polysaccharide potato galactan is actually a mixture of different polysaccharides - Zhangkai Feng; Zhiying Lin; Huazhi Tang; Jie Geng; Yanbo Hu; Kevin H. Mayo; Guihua Tai; Yifa Zhou (Carbohydrate Polymers, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Latest insights on separation and storage of carbon compounds in buildings towards sustainable environment: Recent innovations, challenges, future perspectives and application of machine learning - Zibing Su; Lin Xing; H. Elhosiny Ali; Tamim Alkhalifah; Fahad Alturise; Mohamed Amine Khadimallah; Hamid Assilzadeh (Chemosphere, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Presence of aromatic-rich organic matter and its characterization in grout materials: Implications for radionuclide immobilization - Peng Lin; Chen Xu; Daniel I. Kaplan; Chris M. Yeager; Wei Xing; Ralph Nichols; Peter H. Santschi (Journal of Environmental Radioactivity, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Madden–Julian Oscillation teleconnections to Australian springtime temperature extremes and their prediction in ACCESS-S1 - Andrew G. Marshall; Guomin Wang; Harry H. Hendon; Hai Lin (Climate Dynamics, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

Predicting Drug Synergy and Discovering New Drug Combinations Based on a Graph Autoencoder and Convolutional Neural Network - Huijun Li; Lin Zou; Jamal A. H. Kowah; Dongqiong He; Lisheng Wang; Mingqing Yuan; Xu Liu (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Economic and environmental feasibility of recycling flexible plastic packaging from single stream collection - Yingqian Lin; Michael H. Severson; Ruby T. Nguyen; Anne Johnson; Christopher King; Beth Coddington; Hongqiang Hu; Brennan Madden (Resources, Conservation and Recycling, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Thermal degradation of thaumatin at low pH and its prevention using alkyl gallates - Benjamin Pomon; Yu Zhao; Alex L. Lai; Tiantian Lin; Jack H. Freed; Alireza Abbaspourrad (Food Hydrocolloids, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Late Tonian (ca. 785 Ma) subduction-related mafic-ultramafic cumulates in the West Cathaysia terrane, South China - Lijun Wang; Kexin Zhang; Shoufa Lin; Jean H. Bédard; Gabriel S. Santos; Weihong He; Changqing Yin; Wenjiao Xiao (Precambrian Research, 2023)

Corrosion and bacterial growth mitigation in the desalination plant by imidazolium based ionic liquid: Experimental, surface and molecular docking analysis - Ambrish Singh; K.R. Ansari; Neeta Raj Sharma; Shivani Singh; Rahul Singh; Anu Bansal; Ismat H. Ali; Muhammad Younas; Abdullah K. Alanazi; Yuanhua Lin (Journal of Environmental Chemical Engineering, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Evaluating historic and modern optical techniques for monitoring phytoplankton biomass in the Atlantic Ocean - Robert J. W. Brewin; Jaime Pitarch; Giorgio Dall’Olmo; Hendrik J. van der Woerd; Junfang Lin; Xuerong Sun; Gavin H. Tilstone (Frontiers in Marine Science, 2023)
Traditional measurements of the Secchi depth ( z SD ) and Forel-Ule colour were collected alongside modern radiometric measurements of ocean clarity and colour, and in-situ measurements of chlorophyll-a concentration (Chl-a), on four Atlantic Meridional Transect (AMT) cruises. These data were used to evaluate historic and modern optical techniques for monitoring Chl-a, and to evaluate remote-sensing algorithms. Historic and modern optical measurements were broadly consistent with current understanding, with Secchi depth inversely related to Forel-Ule colour and to beam and diffuse attenuation, positively related to the ratio of blue to green remote-sensing reflectance and euphotic depth. The relationship between Secchi depth and Forel-Ule on AMT was found to be in closer agreement to historical relationships when using data of the Forel-Ule colour of infinite depth, rather than the Forel-Ule colour of the water above the Secchi disk at half z SD . Over the range of 0.03-2.95 mg m -3 , Chl-a was tightly correlated with these optical variables, with the ratio of blue to green remote-sensing reflectance explaining the highest amount of variance in Chl-a (89%), closely followed by the Secchi depth (85%) and Forel-Ule colour (71-81%, depending on the scale used). Existing algorithms that predict Chl-a from these variables were evaluated, and found to perform well, albeit with some systematic differences. Remote sensing algorithms of Secchi depth were in good agreement with in-situ data over the range of values collected (8.5 - 51.8 m, r 2 >0.77, unbiased root mean square differences around 4.5 m), but with a slight positive bias (2.0 - 5.4 m). Remote sensing algorithms of Forel-Ule agreed well with Forel-Ule colour data of infinite water ( r 2 >0.68, mean differences <1). We investigated the impact of environmental conditions and found wind speed to impact the estimation of z SD , and propose a path forward to include the effect of wind in current Secchi depth theory. We discuss the benefits and challenges of collecting measurements of the Secchi depth and Forel-Ule colour and propose future directions for research. Our dataset is made publicly available to support the research community working on the topic.

Evaluation of drought tolerance in sugarcane genotypes using the membership function value of drought tolerance (MFVD) - Chaohua Xu; Jun Mao; Xujuan Li; David M. Burner; Chunjia Li; Shareif H. Hussin Hussin; Xiuqin Lin; Hongbo Liu; Peifang Zhao; Xin Lu; Xinlong Liu (Euphytica, 2023)

Characterizing breast cancer incidence and trends among Asian American, Native Hawaiian, and non-Hispanic White women in Hawaiʻi, 1990-2014 - Ugonna Ihenacho; Meg A. McKinley; Annie Vu; Brenda Y. Hernandez; Lenora W. M. Loo; Scarlett Lin Gomez; Anna H. Wu; Iona Cheng (Cancer Causes & Control, 2023)

Critical insight into sediment microbial fuel cell: Fundamentals, challenges, and perspectives as a barrier to black-odor water formation - Umar Abdulbaki Danhassan; Hongjian Lin; Ibrahim Lawan; Xin Zhang; Mahmoud H. Ali; Aliyu Idris Muhammad; Kuichuan Sheng (Journal of Environmental Chemical Engineering, 2023)

Hemoglobin normalization outperforms other methods for standardizing dried blood spot metabolomics: A comparative study - Abhishek Jain; Montana Morris; Elizabeth Z. Lin; Sajid A. Khan; Xiaomei Ma; Nicole C. Deziel; Krystal J. Godri Pollitt; Caroline H. Johnson (Science of The Total Environment, 2023)

Histone Deacetylase 3 Inhibition Decreases Cerebral Edema and Protects the Blood–Brain Barrier After Stroke - Hui Lu; Ryan Ashiqueali; Chin I Lin; Aashlesha Walchale; Victoria Clendaniel; Rudy Matheson; Marc Fisher; Eng H. Lo; Magdy Selim; Amjad Shehadah (Molecular Neurobiology, 2023)
We have previously shown that selective inhibition of histone deacetylase 3 (HDAC3) decreases infarct volume and improves long-term functional outcomes after stroke. In this study, we examined the effects of HDAC3 inhibition on cerebral edema and blood–brain barrier (BBB) leakage and explored its underlying mechanisms. Adult male Wistar rats were subjected to 2-h middle cerebral artery occlusion (MCAO) and randomly treated i.p. with either vehicle or a selective HDAC3 inhibitor (RGFP966) at 2 and 24 h after stroke. Modified neurological severity scores (mNSS) were calculated at 2 h, 1 day, and 3 days. H&E, Evans blue dye (EBD) assay, and fluorescein isothiocyanate (FITC)-dextran were employed to assess cerebral edema and BBB leakage. Western blot for matrix metalloproteinase-9 (MMP9), MMP-9 zymography, and immunostaining for HDAC3, GFAP, Iba-1, albumin, aquaporin-4, claudin-5, ZO-1, and NF-kB were performed. Early RGFP966 administration decreased cerebral edema ( p = 0.002) and BBB leakage, as measured by EBD assay, FITC-dextran, and albumin extravasation ( p < 0.01). RGFP966 significantly increased tight junction proteins (claudin-5 and ZO-1) in the peri-infarct area. RGFP966 also significantly decreased HDAC3 in GFAP + astrocytes, which correlated with better mNSS ( r = 0.67, p = 0.03) and decreased cerebral edema ( r = 0.64, p = 0.04). RGFP966 decreased aquaporin-4 in GFAP + astrocytes ( p = 0.002), as well as, the inflammatory markers Iba-1, NF-kB, and MMP9 in the ischemic brain ( p < 0.05). Early HDAC3 inhibition decreases cerebral edema and BBB leakage. BBB protection by RGFP966 is mediated in part by the upregulation of tight junction proteins, downregulation of aquaporin-4 and HDAC3 in astrocytes, and decreased neuroinflammation.

Life-course exposure to ambient fine particulate matter and hypertension in adulthood: a longitudinal cohort study - Cui Guo; Ly-yun Chang; Yacong Bo; Changqing Lin; Alexis K. H. Lau; Tony Tam; Xiang Qian Lao (Environmental Science and Pollution Research, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Testing machine learning algorithms on a binary classification phenological model - Wujun Dai; Huiying Jin; Lin Zhou; Tong Liu; Yuhong Zhang; Zhiqiang Zhou; Yongshuo H. Fu; Guangze Jin (Global Ecology and Biogeography, 2023)
Aim Phenological models have become a vital tool for predicting future phenological responses to global climate change. Recently, machine learning (ML) has been used successfully to develop phenological models based on ground observations. However, fitting an observation series that has been observed for only a few years (or even a decade) can easily lead to overfitting, and it is still a great challenge to predict future phenology accurately based on a short observation series. Here, based on historical ground phenological observations, we construct an ML‐based binary classification phenological model that can be applied to temperate trees. Innovation We thoroughly describe the construction process of a species‐specific ML‐based binary classification phenological model that is suitable for phenological predictions in both spring and autumn. Through experiments, we evaluate 18 commonly used ML classification algorithms and the effects of two parameters on the prediction performance of the model. Finally, we compare the performance between the binary classification model and six widely used ecophysiological models for accuracy of spring phenological prediction. Main conclusions The median root mean square error (RMSE) of the binary classification model for the first flowering date (93 observation series) was only 2.99 days, which proves that it is a good method of phenological prediction for temperate trees. This model can effectively overcome the insufficient sample size of ground observations for specific species and provide new insights of phenological predictions for tropical and subtropical trees. The comparison of different ML algorithms showed that the median root mean square errors of the six algorithms were 3.7 days) in prediction of spring phenology. In addition, this model can help us to infer plant physiological mechanisms and drivers of phenological change and provide more accurate predictions of plant phenological responses to climate change.

Identification and characterization of pleiotropic and epistatic QDRL conferring partial resistance to Pythium irregulare and P. sylvaticum in soybean - Feng Lin; Wenlong Li; Austin G. McCoy; Kelly Wang; Janette Jacobs; Na Zhang; Xiaobo Huo; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2022)

Effects of pre-oxidation by ozone, permanganate and ferrate on generation and toxicities of disinfection byproducts - Y. Lin; Y. Lou; A. Li; Y. Wei; H. Li; M. Zhou; Y. Li (International Journal of Environmental Science and Technology, 2022)

Activation of Neuropeptide Y2 Receptor Can Inhibit Global Cerebral Ischemia-Induced Brain Injury - Reggie Hui-Chao Lee; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Alexandre Couto e Silva; Harlee E. Possoit; Garrett A. Clemons; Christina H. Acosta; Victoria A. de la Llama; Jake T. Neumann; Hung Wen Lin (NeuroMolecular Medicine, 2022)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Anomaly and cyber fraud detection in pipelines and supply chains for liquid fuels - Alinne Beteto; Vidal Melo; Jessica Lin; Marwan Alsultan; Eduardo Mario Dias; Elizabeth Korte; DeAndre A. Johnson; Negin Moghadasi; Thomas L. Polmateer; James H. Lambert (Environment Systems and Decisions, 2022)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Water Circulation Driven by Cold Fronts in the Wax Lake Delta (Louisiana, USA) - Qian Zhang; Chunyan Li; Wei Huang; Jun Lin; Matthew Hiatt; Victor H. Rivera-Monroy (Journal of Marine Science and Engineering, 2022)
Atmospheric cold fronts can periodically generate storm surges and affect sediment transport in the Northern Gulf of Mexico (NGOM). In this paper, we evaluate water circulation spatiotemporal patterns induced by six atmospheric cold front events in the Wax Lake Delta (WLD) in coastal Louisiana using the 3-D hydrodynamic model ECOM-si. Model simulations show that channelized and inter-distributary water flow is significantly impacted by cold fronts. Water volume transport throughout the deltaic channel network is not just constrained to the main channels but also occurs laterally across channels accounting for about a quarter of the total flow. Results show that a significant landward flow occurs across the delta prior to the frontal passage, resulting in a positive storm surge on the coast. The along-channel current velocity dominates while cross-channel water transport occurs at the southwest lobe during the post-frontal stage. Depending on local weather conditions, the cold-front-induced flushing event lasts for 1.7 to 7 days and can flush 32–76% of the total water mass out of the system, a greater range of variability than previous reports. The magnitude of water flushed out of the system is not necessarily dependent on the duration of the frontal events. An energy partitioning analysis shows that the relative importance of subtidal energy (10–45% of the total) and tidal energy (20–70%) varies substantially from station to station and is linked to the weather impact. It is important to note that within the WLD region, the weather-induced subtidal energy (46–66% of the total) is much greater than the diurnal tidal energy (13–25% of the total). The wind associated with cold fronts in winter is the main factor controlling water circulation in the WLD and is a major driver in the spatial configuration of the channel network and delta progradation rates.

Effect of pyrolysis temperature on pyrolysis of pine saw dust and application of bio-char - J. Lin; Q. Zhang; H. Xia; S. Cheng (International Journal of Environmental Science and Technology, 2022)

Pathogen resistance in Sphagneticola trilobata (Singapore daisy): molecular associations and differentially expressed genes in response to disease from a widespread fungus - Shan-Shan Qi; Bharani Manoharan; Vignesh Dhandapani; Sridharan Jegadeesan; Susan Rutherford; Justin S. H. Wan; Ping Huang; Zhi-Cong Dai; Dao-Lin Du (Genetica, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Genetic dissection of a pericentromeric region of barley chromosome 6H associated with Fusarium head blight resistance, grain protein content and agronomic traits - Yadong Huang; Lu Yin; Ahmad H. Sallam; Shane Heinen; Lin Li; Karen Beaubien; Ruth Dill-Macky; Yanhong Dong; Brian J. Steffenson; Kevin P. Smith; Gary J. Muehlbauer (Theoretical and Applied Genetics, 2021)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Coarser taxonomic resolutions are informative in revealing fish community abundance trends for the world’s warmest coral reefs - Yu-Jia Lin; Ruben H. Roa-Ureta; Abdullajid Usama Basali; Joselito Francis Albaran Alcaria; Reynaldo Lindo; Mohammad A. Qurban; Perdana K. Prihartato; Ali Qasem; Lotfi Rabaoui (Coral Reefs, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Petrological and isotopic data from Eocene granites in the Luocang area, South Lhasa terrane, Tibet: implications for the India–Eurasia collision - J.-G. Gao; F. Ding; J.-Q. Lin; Q.-H. Zhu; Y. Sun; X.-G. Xie (Australian Journal of Earth Sciences, 2021)

How do different nitrogen application levels and irrigation practices impact biological nitrogen fixation and its distribution in paddy system? - Yanhui Zhang; Tianlong Hu; Hui Wang; Haiyang Jin; Qi Liu; Zhibin Lin; Benjuan Liu; Hongtao Liu; Zhe Chen; Xinwu Lin; Xiaojie Wang; Jing Ma; et al. (Plant and Soil, 2021)

Chronic AdipoRon Treatment Mimics the Effects of Physical Exercise on Restoring Hippocampal Neuroplasticity in Diabetic Mice - Thomas H Lee; Ahadullah; Brian R Christie; Kangguang Lin; Parco Ming-fai Siu; Li Zhang; Ti-fei Yuan; Pragya Komal; Aimin Xu; Kwok-fai So; Suk-yu Yau (Molecular Neurobiology, 2021)
Administration of exercise mimetic drugs could be a novel therapeutic approach to combat comorbid neurodegeneration and metabolic syndromes. Adiponectin is an adipocyte-secreted hormone. In addition to its antidiabetic effect, adiponectin mediates the antidepressant effect of physical exercise associated with adult hippocampal neurogenesis. The antidiabetic effect of the adiponectin receptor agonist AdipoRon has been demonstrated, but its potential pro-cognitive and neurotrophic effects in the hippocampus under diabetic condition are still unclear. This study reported that chronic AdipoRon treatment for 2 weeks improved hippocampal-dependent spatial recognition memory in streptozotocin-induced diabetic mice. Besides, AdipoRon treatment increased progenitor cell proliferation and neuronal differentiation in the hippocampal dentate gyrus (DG) of diabetic mice. Furthermore, AdipoRon treatment significantly increased dendritic complexity, spine density, and N -methyl-D-aspartate receptor-dependent long-term potentiation (LTP) in the dentate region, and increased BDNF levels in the DG of diabetic mice. AdipoRon treatment activated AMPK/PGC-1α signalling in the DG, whereas increases in cell proliferation and LTP were not observed when PGC-1α signalling was pharmacologically inhibited. In sum, chronic AdipoRon treatment partially mimics the benefits of physical exercise for learning and memory and hippocampal neuroplasticity in the diabetic brain. The results suggested that AdipoRon could be a potential physical exercise mimetic to improve hippocampal plasticity and hence rescue learning and memory impairment typically associated with diabetes.

Diversity, Distribution, and Density of Marine Mammals Along the Saudi Waters of the Arabian Gulf: Update From a Multi-Method Approach - Lotfi Rabaoui; Ruben H. Roa-Ureta; Lamia Yacoubi; Yu-Jia Lin; Rommel Maneja; Thadickal V. Joydas; Premlal Panickan; Jinoy Gopalan; Ronald Loughland; Perdana K. Prihartato; Ali Qassem; Tyas I. Hikmawan; et al. (Frontiers in Marine Science, 2021)
Despite the important role of marine mammals in marine ecosystems and the imperative for their conservation, there is still a great lack of information on the diversity, distribution, and density of these animals in the Saudi waters of the Arabian Gulf. To fill this gap, an integrative data-collection approach including fishermen’s questionnaires, opportunistic sighting reports, and directed boat-based surveys, was undertaken between 2016 and 2020, leading to the first scientific report of marine mammal diversity, distribution, and density in the region. The results of the different approaches carried out during the study confirmed a high diversity of cetaceans on the west coast of the study area, with bottlenose dolphins ( Tursiops aduncus ), humpback dolphins ( Sousa plumbea ) and dugongs ( Dugong dugon ) as the most common species. While the two dolphin species were found to be widely distributed in both coastal and offshore waters, D. dugon appears to occur exclusively in coastal waters in the southern part of the study area, mainly in the Gulf of Salwah. The presence of both species of dolphins increased during the summer months and in the vicinity of the numerous oil and gas facilities in this region. The distribution of the observed dolphins was found mostly within a 10–20 km radius around each facility. Other cetacean species observed less frequently in the area include Bryde’s whale ( Balaenoptera edeni ), killer whale ( Orcinus orca ), common dolphin ( Delphinus delphis ) and finless porpoise ( Neophocaena phocaenoides ). Regarding the density of marine mammals in the region, boat-based surveys confirmed the results of fishermen’s questionnaires and reports of opportunistic sightings, with bottlenose and humpback dolphins being the most abundant species. These results provide a baseline for policies oriented to the conservation of mammals in the Saudi waters of the Arabian Gulf.

Molecular mapping of quantitative disease resistance loci for soybean partial resistance to Phytophthora sansomeana - Feng Lin; Wenlong Li; Austin G. McCoy; Xuan Gao; Paul J. Collins; Na Zhang; Zixiang Wen; Sizhe Cao; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2021)

Molecular Level Characterization of Diatom and Coccolithophore-Associated Biopolymers That Are Binding 210Pb and 210Po in Seawater - Peng Lin; Chen Xu; Wei Xing; Peter H. Santschi (Frontiers in Marine Science, 2021)
Through a combination of selective extractions and molecular characterization techniques including Isoelectric Focusing Chromatography and Electrospray Ionization Fourier-Transform Ion Cyclotron Resonance Mass spectrometry, molecular structures of diatom ( Phaeodactylum tricornutum ) and coccolithophore ( Emiliania huxleyi )-associated biopolymers that are responsible for the distinct partitioning behavior between 210 Pb and 210 Po were determined. Our results show that diatom-derived biopolymers have distinctive elemental grouping distributions as compared to those excreted by the coccolithophore, with the former consisting of more heterogeneous elements (i.e., nitrogen, sulfur and phosphorus-containing organic compounds). For the coccolithophore culture, two 210 Pb-enriched biopolymers (non-attached exopolymeric substances and coccosphere shell-associated biopolymers) have a higher abundance of CHO-type compounds, suggesting CHO-only-type compounds as the main binding moieties for 210 Pb. In contrast, such association was not evident in the diatom culture. Different with 210 Pb, 210 Po enrichment in coccolithophore-derived attached exopolymeric substances and Fe-Mn-associated metabolites coincided with the higher abundance of nitrogen/sulfur-containing organic compounds in these two biopolymer fractions, suggesting the strong parallel of Po with the production of nitrogen-rich organic matter as well as sulfur-containing amino acids. These different associations between 210 Pb/ 210 Po and organic functional groups were further explored by separating 210 Pb or 210 Po-labeled coccolithophore-derived biopolymers via isoelectric focusing. This technique suggests that phosphate group-containing molecules but not the other molecules that contain heterogeneous elements (e.g., CHONS, CHON, and CHOS) as the strongest binding agents for 210 Pb, while the more hydrophobic (high protein to carbohydrate ratio) nitrogen/sulfur-enriched organic moieties acted as the main 210 Po-binding ligands. It is concluded that the deficiency of 210 Po with respect to 210 Pb can be influenced by the relative abundance of nitrogen/sulfur-enriched organic moieties to the nitrogen/sulfur-depleted organic compounds in the water column. This behavior constrains the application of 210 Po- 210 Pb approach to quantify the particulate organic carbon (POC) export flux in the ocean. It also explains that differences in chemical binding of the 210 Po as compared to those of other radionuclides (e.g., thorium-234) as the main factor. That suggests that differences in decay half-lives or physical factors are less important when these nuclides are applied to estimate the POC flux in the ocean.

Correction to: Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
A correction to this paper has been published: 10.1007/s12035-021-02310-3

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
Sigma-1 receptors (Sig-1Rs) are endoplasmic reticulum (ER) chaperones implicated in neuropathic pain. Here we examine if the Sig-1R may relate to neuropathic pain at the level of dorsal root ganglia (DRG). We focus on the neuronal excitability of DRG in a “spare nerve injury” (SNI) model of neuropathic pain in rats and find that Sig-1Rs likely contribute to the genesis of DRG neuronal excitability by decreasing the protein level of voltage-gated Cav2.2 as a translational inhibitor of mRNA. Specifically, during SNI, Sig-1Rs translocate from ER to the nuclear envelope via a trafficking protein Sec61β. At the nucleus, the Sig-1R interacts with cFos and binds to the promoter of 4E-BP1, leading to an upregulation of 4E-BP1 that binds and prevents eIF4E from initiating the mRNA translation for Cav2.2. Interestingly, in Sig-1R knockout HEK cells, Cav2.2 is upregulated. In accordance with those findings, we find that intra-DRG injection of Sig-1R agonist (+)pentazocine increases frequency of action potentials via regulation of voltage-gated Ca2+ channels. Conversely, intra-DRG injection of Sig-1R antagonist BD1047 attenuates neuropathic pain. Hence, we discover that the Sig-1R chaperone causes neuropathic pain indirectly as a translational inhibitor.

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Strengths and weaknesses in the long‐term sustainability of two sympatric seabreams ( Argyrops spinifer and Rhabdosargus haffara , S paridae) - Yu‐Jia Lin; Lotfi Rabaoui; Rommel H. Maneja; Abdu Rahiman Kambrath Pulikkoden; Panickan Premlal; Zahid Nazeer; Mohammad A. Qurban; Khaled Abdulkader; Perdana K. Prihartato; Ali M. Qasem; Nabil Fita; Ruben H. Roa‐Ureta (Journal of Fish Biology, 2021)
Argyrops spinifer and Rhabdosargus haffara are two sympatric seabream species making important contributions to fisheries landings in the western Arabian/Persian Gulf. We identified the strengths and weaknesses in the long‐term sustainability of A. spinifer and R. haffara stocks by integrating multiple sources of data, including fisheries catch and effort statistics, life history traits, scientific trawl surveys and historical length frequency distribution. Four strengths were identified in A. spinifer : wide distribution of juveniles, positive association to the network of de facto fishing exclusion areas created by hundreds of oil‐gas facilities, early maturation and the existence of large and old individuals. A. spinifer suffers from two potential weaknesses: slow growth rate and higher exploitation pressure on the small‐sized individuals. R. haffara , on the other hand, has a strength of having a short life span and a fast growth rate, characteristics that make it robust to unfavourable conditions. R. haffara suffers from two weaknesses: the lack of association to the oil and gas facilities, and the preference for nearshore shallow waters with stronger negative anthropogenic impacts. Identified strengths and weaknesses of these two sparids provided a preliminary assessment about their long‐term sustainability, as well as a roadmap about how to develop different management strategies to meet specific objectives.

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Genetic Diversity in Marine Planktonic Ciliates (Alveolata, Ciliophora) Suggests Distinct Geographical Patterns – Data From Chinese and European Coastal Waters - Maximilian H. Ganser; Dominik Forster; Weiwei Liu; Xiaofeng Lin; Thorsten Stoeck; Sabine Agatha (Frontiers in Marine Science, 2021)
Unraveling geographic distribution patterns of planktonic protists is a central goal in marine microbial ecology. Using a novel combination of recently developed phylogenetic and network analyses on a V4 18S rDNA metabarcoding dataset, we here analyzed the genetic diversity of marine planktonic ciliate communities in Chinese and European coastal waters. Thereby, our approach provided an unprecedented perspective on geographic patterns inferred from ciliate genetic diversity and accomplished a very fine resolution down to single nucleotides within operational taxonomic units (OTUs). While most OTUs (87%) exclusively contained sequences of either Chinese or European origin, those OTUs detected in both regions comprised the vast majority of reads (84%). Phylogenetic analyses of OTUs belonging to the same taxon revealed genetically distinct clades that were geographically restricted to either Chinese or European coastal waters. The detection of signature nucleotides emphasized this genetic distinction of Chinese and European clades. Second-level clustering of OTUs and reference sequences in two selected taxa (the oligotrichid Spirotontonia and the tintinnid Tintinnidium ) revealed the presence of several potentially new species or ones lacking genetic reference data. Geographic patterns were also discovered by network analyses within 700 widespread and abundant OTUs; in 77 of these OTUs, European and Chinese sequences formed significantly assortative groups. These assortative groupings indicated a higher genetic similarity among sequences from the same region than between sequences from different regions. Our results demonstrate that detailed analyses of metabarcoding data down to single nucleotide differences expand our perception of geographical distribution patterns and provide insights into historic and ongoing effective dispersal in protists. The congruent discovery of geographic patterns at different levels of resolution (between and within OTUs) suggests that cosmopolitan distribution in marine planktonic ciliates is less common than previously postulated.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Unexpected meteotsunamis prior to Typhoon Wipha and Typhoon Neoguri - Li-Ching Lin; Chin H. Wu (Natural Hazards, 2021)

Evaluation of favourable hot dry rock areas in the east of the Yishu fault zone in China - Q. Deng; A. Jiang; Z. Tong; H. Lin; Z. Gao; X. Sun; M. Nie (Australian Journal of Earth Sciences, 2021)

Correction to: Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2021)

Modeling motor task activation from resting-state fMRI using machine learning in individual subjects - Chen Niu; Alexander D. Cohen; Xin Wen; Ziyi Chen; Pan Lin; Xin Liu; Bjoern H. Menze; Benedikt Wiestler; Yang Wang; Ming Zhang (Brain Imaging and Behavior, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Viet D. H. Dang; Pak-Yin Cheung; Chia-Ling Fong; Aziz J. Mulla; Jia-Ho Shiu; Che-Hung Lin; Yoko Nozawa (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along three coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of six key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins ( Echinothrix spp. and Diadema spp.) dominated most sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider monitoring locally remnant herbivores and incorporating them into management strategies.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Incorporation of Hydroxamate Siderophore and Associated Fe Into Marine Particles in Natural Seawater - Peng Lin; Chen Xu; Luni Sun; Wei Xing; Peter H. Santschi (Frontiers in Marine Science, 2020)

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

Shifts in the bacterial community along with root-associated compartments of maize as affected by goethite - Peduruhewa H Jeewani; Lin Chen; Lukas Van Zwieten; Congcong Shen; Georg Guggenberger; Yu Luo; Jianming Xu (Biology and Fertility of Soils, 2020)

Advanced psychometric testing on a clinical screening tool to evaluate insomnia: sleep condition indicator in patients with advanced cancer - Chung-Ying Lin; Andy S. K. Cheng; Vida Imani; Mohsen Saffari; Maurice M. Ohayon; Amir H. Pakpour (Sleep and Biological Rhythms, 2020)
Purpose To examine the psychometric properties of the Sleep Condition Indicator (SCI) using different psychometric approaches [including classical test theory, Rasch models, and receiver operating characteristics (ROC) curve] among patients with advanced cancer. Methods Through convenience sampling, patients with cancer at stage III or IV ( n = 859; 511 males; mean ± SD age = 67.4 ± 7.5 years) were recruited from several oncology units of university hospitals in Iran. All the participants completed the SCI, Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), and Edmonton Symptom Assessment Scale (ESAS). In addition, 491 participants wore an actigraph device to capture objective sleep. Results Classical test theory [factor loadings from confirmatory factor analysis = 0.76–0.89; test–retest reliability = 0.80–0.93] and Rasch analysis [infit mean square (MnSq) = 0.63–1.31; outfit MnSq = 0.61–1.23] both support the construct validity of the SCI. The SCI had significant associations with ISI, PSQI, ESS, HADS, GHQ, and ESAS. In addition, the SCI has satisfactory area under ROC curve (0.92) when comparing a gold standard of insomnia diagnosis. Significant differences in the actigraphy measure were found between insomniacs and non-insomniacs based on the SCI score defined by ROC. Conclusion With the promising psychometric properties shown in the SCI, healthcare providers can use this simple assessment tool to target the patients with advanced cancer who are at risk of insomnia and subsequently provide personalized care efficiently.

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Oxidation of nine petroleum hydrocarbon compounds by combined hydrogen peroxide/sodium persulfate catalyzed by siderite - YueHua Li; Lin Zhao; Fulong Chen; Kylan S. Jin; Paul H. Fallgren; Liang Chen (Environmental Science and Pollution Research, 2020)

Doping TiO2 with CuSO4 enhances visible light photocatalytic activity for organic pollutant degradation - Mark Daniel G. de Luna; Sergi Garcia-Segura; Chinee H. Mercado; Yao-Tung Lin; Ming-Chun Lu (Environmental Science and Pollution Research, 2020)

Waiting and “weighted down”: the challenge of anticipatory loss for individuals and families with Li-Fraumeni Syndrome - Allison Werner-Lin; Jennifer L. Young; Catherine Wilsnack; Shana L. Merrill; Victoria Groner; Mark H. Greene; Payal P. Khincha (Familial Cancer, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

Formation mechanism of a rainfall triggered complex landslide in southwest China - Qiu-xiang Huang; Xiang-tao Xu; P. H. S. W. Kulatilake; Feng Lin (Journal of Mountain Science, 2020)

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

A new slice-based method for calculating the minimum safe thickness for a filled-type karst cave - Z. H. Xu; X. Huang; S. C. Li; P. Lin; X. S. Shi; J. Wu (Bulletin of Engineering Geology and the Environment, 2020)

Dietary Selenium Supplementation Does Not Attenuate Mammary Tumorigenesis-Mediated Bone Loss in Male MMTV-PyMT Mice - Lin Yan; Forrest H. Nielsen; Sneha Sundaram; Jay Cao (Biological Trace Element Research, 2020)

Experimental and Analytical Investigations of the Effect of Hole Size on Borehole Breakout Geometries for Estimation of In Situ Stresses - H. Lin; J. Oh; I. Canbulat; T. R. Stacey (Rock Mechanics and Rock Engineering, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

Managing water quality in a river basin with uncertainty - H.-W. Chen; W.-Y. Chen; C.-T. Wang; Y.-H. Lin; M.-J. Deng; C.-Y. Chiang (International Journal of Environmental Science and Technology, 2020)

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of different inhibitors such as malonic acid, Na3PO4 and HgCl2 on uptake of different forms of antimony in rice plant - RenWei Feng; Lei Lei; BiXiu Liu; WenXiang Chen; RuiRui Zhang; LiZhen Wang; YuanPing Li; JunMing Su; JiaXin Dai; RenJie Wang; ZiTing Lin; Ibtissem Ben Fekih; et al. (Plant and Soil, 2019)

Life history traits and temporal trends of abundance of the orange‐spotted trevally ( Carangoides bajad ) from Saudi waters of the Gulf - Yu‐Jia Lin; Lotfi Rabaoui; Rommel H. Maneja; Mohammad A. Qurban; Khaled Abdulkader; Hussain Al‐Nazry; Ruben H. Roa‐Ureta (Journal of Fish Biology, 2019)
In this study we lay the groundwork for sustainability‐oriented fisheries management, by estimating parameters the life history of orange‐spotted trevally Carangoides bajad as well as trends of abundance in coral‐reef habitats. We observed a new record of maximum size of 720 mm fork length. Carangoides bajad is a moderately long‐lived (14 years) and slow‐growing ( K = 0.085 year −1 ) carangid species, closer to a K‐selection species, with higher vulnerability to fishing and lower rates of recovery when the population level is low. Growth and biological composition in terms of length and age categories do not differ between the sexes, but females become mature faster. Reproductively active months (May–August) overlapped with those from Emirati waters further south. The abundance index showed a pronounced drop during 1990–1993, possibly in connection with habitat deterioration during the Gulf War (1990–1991) oil spill. The index increased gradually from 1994 and has fluctuated close to the reference level of 1985 up to the present. Considering the findings of large‐sized and old‐age individuals and abundance index from coral reefs close to its level three decades back, the C. bajad stock in the western part of The Gulf appears to be in healthy exploitation status despite growing harvesting rates.

Global travertine deposition modulated by oscillations in climate - Jason W. Ricketts; Lin Ma; Amy E. Wagler; Victor H. Garcia (Journal of Quaternary Science, 2019)
Travertine deposits are important records of past fluid flow in the Earth's crust, and document fluid migration through both tectonic activity and changes in climate. While many studies hint at possible relationships between travertine formation and global climate, none have investigated these connections on a global scale. Here we compile 1649 published travertine ages from six continents to test the hypothesis that global and/or regional changes in climate regulate travertine deposition. Peaks in bedded travertine ages occur with main frequencies that correspond to 100‐kyr changes in global climate, where most peaks occur during glacial terminations or interglacial periods, including a large peak that coincides with the Early Holocene climatic optimum. Time–series analysis also suggests a possible connection with 41‐kyr obliquity cycles. At regional scales, many peaks also correspond with local times of high precipitation or wet conditions. This can be attributed to higher groundwater recharge rates, providing the necessary water to form travertine. Many bedded travertine‐depositing systems may therefore be water‐limiting and sufficient CO 2 may be present even during times of no travertine deposition. Exceptions to this conclusion are banded vein travertine deposits, which typically form during times of dry climate when water tables are low. Copyright © 2019 John Wiley & Sons, Ltd.

The asymmetric function of Dph1–Dph2 heterodimer in diphthamide biosynthesis - Min Dong; Emily E. Dando; Ilana Kotliar; Xiaoyang Su; Boris Dzikovski; Jack H. Freed; Hening Lin (JBIC Journal of Biological Inorganic Chemistry, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Tsunami Hazard and Built Environment Damage Observations from Palu City after the September 28 2018 Sulawesi Earthquake and Tsunami - Ryan Paulik; Aditya Gusman; James H. Williams; Gumbert Maylda Pratama; Sheng-lin Lin; Alamsyah Prawirabhakti; Ketut Sulendra; Muhammad Yasser Zachari; Zabin Ellyni Dwi Fortuna; Novita Barrang Pare Layuk; Ni Wayan Ika Suwarni (Pure and Applied Geophysics, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Evaluation of the performance of IAP-AGCM4.1 in simulating the climate of West Africa - M. O. Adeniyi; Z. Lin; H. Zhang (Theoretical and Applied Climatology, 2019)

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

Cr-induced disturbance on expression of six COX genes in rice seedlings - X.-Z. Yu; C.-J. Lu; Y.-J. Lin; Y.-H. Li (International Journal of Environmental Science and Technology, 2019)

Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2019)

Recombinant FGF21 Protects Against Blood-Brain Barrier Leakage Through Nrf2 Upregulation in Type 2 Diabetes Mice - Zhanyang Yu; Li Lin; Yinghua Jiang; Ian Chin; Xiaojie Wang; Xiaokun Li; Eng H. Lo; Xiaoying Wang (Molecular Neurobiology, 2019)

The role of heterogeneous environment and docetaxel gradient in the emergence of polyploid, mesenchymal and resistant prostate cancer cells - Ke-Chih Lin; Gonzalo Torga; Yusha Sun; Robert Axelrod; Kenneth J. Pienta; James C. Sturm; Robert H. Austin (Clinical & Experimental Metastasis, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Responses of legumes and grasses to non-, moderate, and dense shade in Missouri, USA. I. Forage yield and its species-level plasticity - Kejia Pang; J. W. Van Sambeek; Nadia E. Navarrete-Tindall; Chung-Ho Lin; Shibu Jose; H. E. Garrett (Agroforestry Systems, 2019)

Responses of legumes and grasses to non-, moderate, and dense shade in Missouri, USA. II. Forage quality and its species-level plasticity - Kejia Pang; J. W. Van Sambeek; Nadia E. Navarrete-Tindall; Chung-Ho Lin; Shibu Jose; H. E. Garrett (Agroforestry Systems, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

Carbon steel slag and stainless steel slag for removal of arsenic from stimulant and real groundwater - W. Shi; H. Li; G. Liao; G. Pei; Y. Lin (International Journal of Environmental Science and Technology, 2018)

Co-Delivery of Ciprofloxacin and Colistin in Liposomal Formulations with Enhanced In Vitro Antimicrobial Activities against Multidrug Resistant Pseudomonas aeruginosa - Shaoning Wang; Shihui Yu; Yuwei Lin; Peizhi Zou; Guihong Chai; Heidi H. Yu; Hasini Wickremasinghe; Nivedita Shetty; Junhong Ling; Jian Li; Qi Zhou (Pharmaceutical Research, 2018)

Black race and distant recurrence after neoadjuvant or adjuvant chemotherapy in breast cancer - Jessica M. Pastoriza; George S. Karagiannis; Juan Lin; Sonali Lanjewar; David Entenberg; John S. Condeelis; Joseph A. Sparano; Xiaonan Xue; Thomas E. Rohan; Maja H. Oktay (Clinical & Experimental Metastasis, 2018)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Before and after: craving, mood, and background stress in the hours surrounding drug use and stressful events in patients with opioid-use disorder - Kenzie L. Preston; William J. Kowalczyk; Karran A. Phillips; Michelle L. Jobes; Massoud Vahabzadeh; Jia-Ling Lin; Mustapha Mezghanni; David H. Epstein (Psychopharmacology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Endocrine-Disrupting Activities and Organic Contaminants Associated with Oil and Gas Operations in Wyoming Groundwater - Christopher D. Kassotis; Danh C. Vu; Phuc H. Vo; Chung-Ho Lin; Jennifer N. Cornelius-Green; Sharyle Patton; Susan C. Nagel (Archives of Environmental Contamination and Toxicology, 2018)

Species composition, functional and phylogenetic distances correlate with success of invasive Chromolaena odorata in an experimental test - Yu‐Long Zheng; Jean H. Burns; Zhi‐Yong Liao; Yang‐ping Li; Jie Yang; Ya‐jun Chen; Jiao‐lin Zhang; Yu‐guo Zheng (Ecology Letters, 2018)
Biotic resistance may influence invasion success; however, the relative roles of species richness, functional or phylogenetic distance in predicting invasion success are not fully understood. We used biomass fraction of Chromolaena odorata , an invasive species in tropical and subtropical areas, as a measure of ‘invasion success’ in a series of artificial communities varying in species richness. Communities were constructed using species from Mexico (native range) or China (non‐native range). We found strong evidence of biotic resistance: species richness and community biomass were negatively related with invasion success; invader biomass was greater in plant communities from China than from Mexico. Harvesting time had a greater effect on invasion success in plant communities from China than on those from Mexico. Functional and phylogenetic distances both correlated with invasion success and more functionally distant communities were more easily invaded. The effects of plant‐soil fungi and plant allelochemical interactions on invasion success were species‐specific.

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

FGF21 Attenuates High-Fat Diet-Induced Cognitive Impairment via Metabolic Regulation and Anti-inflammation of Obese Mice - Qingzhi Wang; Jing Yuan; Zhanyang Yu; Li Lin; Yinghua Jiang; Zeyuan Cao; Pengwei Zhuang; Michael J. Whalen; Bo Song; Xiao-Jie Wang; Xiaokun Li; Eng H. Lo; et al. (Molecular Neurobiology, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Comparison of endosperm amyloplast development and degradation in waxy and non-waxy wheat - H. Yu; Y. Yang; X.Y. Chen; G.X. Lin; J.Y. Sheng; J.Y. Nie; Q.J. Wang; E.J. Zhang; X.R. Yu; Z. Wang; F. Xiong (Cereal Research Communications, 2018)

Formation and characteristics of the Xiaoba landslide in Fuquan, Guizhou, China - F. Lin; L. Z. Wu; R. Q. Huang; H. Zhang (Landslides, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Late sodium current associated cardiac electrophysiological and mechanical dysfunction - Shandong Yu; Gang Li; Christopher L.-H. Huang; Ming Lei; Lin Wu (Pflügers Archiv - European Journal of Physiology, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

The Asian–Bering–North American teleconnection: seasonality, maintenance, and climate impact on North America - Bin Yu; H. Lin; Z. W. Wu; W. J. Merryfield (Climate Dynamics, 2018)

Optical types of inland and coastal waters - Evangelos Spyrakos; Ruth O'Donnell; Peter D. Hunter; Claire Miller; Marian Scott; Stefan G. H. Simis; Claire Neil; Claudio C. F. Barbosa; Caren E. Binding; Shane Bradt; Mariano Bresciani; Giorgio Dall'Olmo; et al. (Limnology and Oceanography, 2018)
Inland and coastal waterbodies are critical components of the global biosphere. Timely monitoring is necessary to enhance our understanding of their functions, the drivers impacting on these functions and to deliver more effective management. The ability to observe waterbodies from space has led to Earth observation (EO) becoming established as an important source of information on water quality and ecosystem condition. However, progress toward a globally valid EO approach is still largely hampered by inconsistences over temporally and spatially variable in‐water optical conditions. In this study, a comprehensive dataset from more than 250 aquatic systems, representing a wide range of conditions, was analyzed in order to develop a typology of optical water types (OWTs) for inland and coastal waters. We introduce a novel approach for clustering in situ hyperspectral water reflectance measurements ( n = 4045) from multiple sources based on a functional data analysis. The resulting classification algorithm identified 13 spectrally distinct clusters of measurements in inland waters, and a further nine clusters from the marine environment. The distinction and characterization of OWTs was supported by the availability of a wide range of coincident data on biogeochemical and inherent optical properties from inland waters. Phylogenetic trees based on the shapes of cluster means were constructed to identify similarities among the derived clusters with respect to spectral diversity. This typification provides a valuable framework for a globally applicable EO scheme and the design of future EO missions.

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Biofilm community structure and the associated drag penalties of a groomed fouling release ship hull coating - Kelli Z. Hunsucker; Gary J. Vora; J. Travis Hunsucker; Harrison Gardner; Dagmar H. Leary; Seongwon Kim; Baochuan Lin; Geoffrey Swain (Biofouling, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Challenges of Antibody Drug Conjugates in Cancer Therapy: Current Understanding of Mechanisms and Future Strategies - Jiunn H. Lin; Yue Guo; Weirong Wang (Current Pharmacology Reports, 2018)

Aerosol microphysical and radiative effects on continental cloud ensembles - Yuan Wang; Jonathan M. Vogel; Yun Lin; Bowen Pan; Jiaxi Hu; Yangang Liu; Xiquan Dong; Jonathan H. Jiang; Yuk L. Yung; Renyi Zhang (Advances in Atmospheric Sciences, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The Quantitative Structural and Compositional Analyses of Degenerating Intervertebral Discs Using Magnetic Resonance Imaging and Contrast-Enhanced Micro-Computed Tomography - Kevin H. Lin; Simon Y. Tang (Annals of Biomedical Engineering, 2017)

Acclimation of bloom‐forming and perennial seaweeds to elevated p CO 2 conserved across levels of environmental complexity - Dong Xu; Charlotte‐Elisa Schaum; Fan Lin; Ke Sun; James R. Munroe; Xiao W. Zhang; Xiao Fan; Lin H. Teng; Yi T. Wang; Zhi M. Zhuang; Naihao Ye (Global Change Biology, 2017)
Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO 2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO 2 levels ranging from 400 to 2,000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO 2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds.

Intra- and Intergenomic variation of Ploidy and Clonality characterize Phytophthora capsici on Capsicum sp. in Taiwan - Derek W. Barchenger; Kurt H. Lamour; Zong-Ming Sheu; Sandesh Shrestha; Sanjeet Kumar; Shih-Wen Lin; Rishi Burlakoti; Paul W. Bosland (Mycological Progress, 2017)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Context and craving during stressful events in the daily lives of drug-dependent patients - Kenzie L. Preston; William J. Kowalczyk; Karran A. Phillips; Michelle L. Jobes; Massoud Vahabzadeh; Jia-Ling Lin; Mustapha Mezghanni; David H. Epstein (Psychopharmacology, 2017)

Identification of a seed coat-specific promoter fragment from the Arabidopsis MUCILAGE-MODIFIED4 gene - Gillian H. Dean; Zhaoqing Jin; Lin Shi; Elahe Esfandiari; Robert McGee; Kylie Nabata; Tiffany Lee; Ljerka Kunst; Tamara L. Western; George W. Haughn (Plant Molecular Biology, 2017)

Rethinking communication in risk interpretation and action - Shabana Khan; Jyoti L. Mishra; Kuna-hui Elaine Lin; Emma E. H. Doyle (Natural Hazards, 2017)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Experimental Investigation of the Anisotropic Mechanical Properties of a Columnar Jointed Rock Mass: Observations from Laboratory-Based Physical Modelling - H. Ji; J. C. Zhang; W. Y. Xu; R. B. Wang; H. L. Wang; L. Yan; Z. N. Lin (Rock Mechanics and Rock Engineering, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

TRPV4 Activation Contributes Functional Recovery from Ischemic Stroke via Angiogenesis and Neurogenesis - Chun-Kai Chen; Po-Yuan Hsu; Tzu-Ming Wang; Zhi-Feng Miao; Ruey-Tay Lin; Suh-Hang H. Juo (Molecular Neurobiology, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

RETRACTED ARTICLE: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Cytotoxic effects of the anthraquinone derivatives 1′-deoxyrhodoptilometrin and (S)-(−)-rhodoptilometrin isolated from the marine echinoderm Comanthus sp. - Wim Wätjen; Sherif S. Ebada; Anja Bergermann; Yvonni Chovolou; Frank Totzke; Michael H. G. Kubbutat; Wenhan Lin; Peter Proksch (Archives of Toxicology, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

The genus Fusariella - Chuan-Gen Lin; Yun Chen; Eric H. C. McKenzie; Darbhe J. Bhat; Hiran A. Ariyawansa; Kevin D. Hyde; Yong Wang (Mycological Progress, 2016)

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Extracellular Cl− regulates human SO4 2−/anion exchanger SLC26A1 by altering pH sensitivity of anion transport - Meng Wu; John F. Heneghan; David H. Vandorpe; Laura I. Escobar; Bai-Lin Wu; Seth L. Alper (Pflügers Archiv - European Journal of Physiology, 2016)

The Aggregation Pheromone of Phyllotreta striolata (Coleoptera: Chrysomelidae) Revisited - Franziska Beran; Guillermo H. Jiménez-Alemán; Mei-ying Lin; Yun-Che Hsu; Inga Mewis; Ramasamy Srinivasan; Christian Ulrichs; Wilhelm Boland; Bill S. Hansson; Andreas Reinecke (Journal of Chemical Ecology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The impact of global budgeting on health service utilization, health care expenditures, and quality of care among patients with pneumonia in Taiwan - C.-Y. Lin; T. Ma; C.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Biodegradation of atrazine by Arthrobacter sp. C3, isolated from the herbicide-contaminated corn field - H. Wang; Y. Liu; J. Li; M. Lin; X. Hu (International Journal of Environmental Science and Technology, 2016)

Cortical thickness and surface area in neonates at high risk for schizophrenia - Gang Li; Li Wang; Feng Shi; Amanda E. Lyall; Mihye Ahn; Ziwen Peng; Hongtu Zhu; Weili Lin; John H. Gilmore; Dinggang Shen (Brain Structure and Function, 2016)

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Influence of Regional Difference in Bone Mineral Density on Hip Fracture Site in Elderly Females by Finite Element Analysis - Z. L. Lin; P. F. Li; Z. H. Pang; X. H. Zheng; F. Huang; H. H. Xu; Q. L. Li (Cell Biochemistry and Biophysics, 2015)

A Numerical Study of Water Loss Rate Distributions in MDCT-Based Human Airway Models - Dan Wu; Shinjiro Miyawaki; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2015)

Some of the people, some of the time: field evidence for associations and dissociations between stress and drug use - Melody Furnari; David H. Epstein; Karran A. Phillips; Michelle L. Jobes; William J. Kowalczyk; Massoud Vahabzadeh; Jia-Ling Lin; Kenzie L. Preston (Psychopharmacology, 2015)

Melatonin Ameliorates Arsenite-Induced Neurotoxicity: Involvement of Autophagy and Mitochondria - Y. C. Teng; Y. I. Tai; H. J. Huang; A. M. Y. Lin (Molecular Neurobiology, 2015)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Neonatal urinary tract infection may increase the risk of childhood asthma - C.-H. Lin; Y.-C. Wang; W.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Robust Endoplasmic Reticulum-Associated Degradation of Rhodopsin Precedes Retinal Degeneration - Wei-Chieh Chiang; Heike Kroeger; Sanae Sakami; Carissa Messah; Douglas Yasumura; Michael T. Matthes; Judith A. Coppinger; Krzysztof Palczewski; Matthew M. LaVail; Jonathan H. Lin (Molecular Neurobiology, 2015)

The application of the cluster identification method for the detection of leakages in water distribution networks - H.-Y. Lin; B.-W. Lin; P.-H. Li; J.-J. Kao (International Journal of Environmental Science and Technology, 2015)

Effects of a sharp change of emergent vegetation distributions on thermally driven flow over a slope - Ying-Tien Lin; Chin H. Wu (Environmental Fluid Mechanics, 2015)

Overexpression of AT14A confers tolerance to drought stress-induced oxidative damage in suspension cultured cells of Arabidopsis thaliana - Lin Wang; Jie He; Haidong Ding; Hui Liu; Bing Lü; Jiansheng Liang; L. Wang; J. He; H. D. Ding; H. Liu; B. Lü; J. S. Liang (Protoplasma, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Survival among Black and White patients with renal cell carcinoma in an equal-access health care system - Jie Lin; Shelia H. Zahm; Craig D. Shriver; Mark Purdue; Katherine A. McGlynn; Kangmin Zhu (Cancer Causes & Control, 2015)

Association between plasma adiponectin levels and colorectal cancer risk in women - Paulette D. Chandler; Julie E. Buring; JoAnn E. Manson; M. V. Moorthy; Shumin Zhang; I-Min Lee; Jennifer H. Lin (Cancer Causes & Control, 2015)

Pilot study of mold in homes of asthmatic children in Taipei, Taiwan, using the Environmental Relative Moldiness Index - Chi-Hsien Chen; H. Jasmine Chao; Wei-Chiang Shen; Bing-Yu Chen; King-Teh Lin; Yue Leon Guo; Stephen Vesper (Aerobiologia, 2015)

Balanitis is a risk factor for herpes zoster - C.-Y. Hsu; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Surgical Treatment of Hashimoto’s with Thyroid Microcarcinoma - Liu Tao; H. Xi-lin; M. Xiang-dong (Cell Biochemistry and Biophysics, 2015)

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Persistent organic pollutants in tropical coastal and offshore environment: part A—atmospheric polycyclic aromatic hydrocarbons - I.-C. Lai; C.-L. Lee; F.-C. Ko; J.-C. Lin; H.-C. Huang (International Journal of Environmental Science and Technology, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Pharmacokinetic interaction between HCV protease inhibitor boceprevir and methadone or buprenorphine in subjects on stable maintenance therapy - Ellen G. J. Hulskotte; R. Douglas Bruce; Hwa-Ping Feng; Lynn R. Webster; Feng Xuan; Wen H. Lin; Edward O’Mara; John A. Wagner; Joan R. Butterton (European Journal of Clinical Pharmacology, 2015)

Development of human brain cortical network architecture during infancy - Wei Gao; Sarael Alcauter; J. Keith Smith; John H. Gilmore; Weili Lin (Brain Structure and Function, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Polarization of excitation light influences molecule counting in single-molecule localization microscopy - Ye Chen; Han Lin; Mandy J. Ludford-Menting; Andrew H. Clayton; Min Gu; Sarah M. Russell (Histochemistry and Cell Biology, 2015)

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study - C.-Y. Lai; T.-Y. Yang; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

The complex interplay among bacterial motility and virulence factors in different Escherichia coli infections - C. Y. Kao; W. H. Lin; C. C. Tseng; A. B. Wu; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The role of rooted emergent vegetation on periodically thermal-driven flow over a sloping bottom - Ying-Tien Lin; Chin H. Wu (Environmental Fluid Mechanics, 2014)

Numerical modeling of a strong dust event over the south China region in March 2010 - Kim-Chiu Chow; Lin Su; Jimmy C. H. Fung; Hui Ma; Alexis K. H. Lau (Meteorology and Atmospheric Physics, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effect of nano-hematite morphology on photocatalytic activity - Y. H. Chen; C. C. Lin (Physics and Chemistry of Minerals, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

The first record, tagging and release of a neonatal whale shark Rhincodon typus in Taiwan - H. H. Hsu; C. Y. Lin; S. J. Joung (Journal of Fish Biology, 2014)
On 27 October 2013, a Rhincodon typus was apparently chased by a group of Caranx ignobilis into nearshore waters near Green Island (Ludao), east of Taiwan. A fisherman brought it back to port where it was kept in a small sea pen until release. The R. typus was 78 cm total length, and was tagged and released on 29 October 2013.

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

Modeling chromium(VI) reduction by Escherichia coli 33456 using ceramic pearl as a supporting medium - Y.-H. Lin (International Journal of Environmental Science and Technology, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

On the origin of water-soluble organic tracer compounds in fine aerosols in two cities: the case of Los Angeles and Barcelona - M. Alier; M. Dall Osto; Y.-H. Lin; J. D. Surratt; R. Tauler; J. O. Grimalt; B. L. van Drooge (Environmental Science and Pollution Research, 2014)

A Numerical Study of Heat and Water Vapor Transfer in MDCT-Based Human Airway Models - Dan Wu; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2014)

Convergent transcription through microsatellite repeat tracts induces cell death - William Y. Lin; Yunfu Lin; John H. Wilson (Molecular Biology Reports, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Clinical and microbiological characteristics of Klebsiella pneumoniae from community-acquired recurrent urinary tract infections - W. H. Lin; C. Y. Kao; D. C. Yang; C. C. Tseng; A. B. Wu; C. H. Teng; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pharmacokinetic and pharmacodynamic interactions between the hepatitis C virus protease inhibitor, boceprevir, and the oral contraceptive ethinyl estradiol/norethindrone - Wen H. Lin; Hwa-Ping Feng; Craig R. Shadle; Terry O’Reilly; John A. Wagner; Joan R. Butterton (European Journal of Clinical Pharmacology, 2014)

Evaluation of seedling resistance of rice germplasm resources to sheath blight (Rhizoctonia solani) - B. Chen; L.-W. Li; Y.-J. Lin; Z.-H. Wang; G.-D. Lu (Cereal Research Communications, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Production GH transgenic goat improving mammogenesis by somatic cell nuclear transfer - Q. Zhang; J. Q. Chen; J. Lin; Q. H. Yu; H. Q. Yu; X. J. Xu; G. H. Liu; Q. Yang (Molecular Biology Reports, 2014)

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

The Copper Balance of Cities - Ulrich Kral; Chih‐Yi Lin; Katharina Kellner; Hwong‐wen Ma; Paul H. Brunner (Journal of Industrial Ecology, 2014)
Summary Material management faces a dual challenge: on the one hand satisfying large and increasing demands for goods and on the other hand accommodating wastes and emissions in sinks. Hence, the characterization of material flows and stocks is relevant for both improving resource efficiency and environmental protection. This article focuses on the urban scale, a dimension rarely investigated in past metal flow studies. We compare the copper (Cu) metabolism of two cities in different economic states, namely, Vienna (Europe) and Taipei (Asia). Substance flow analysis is used to calculate urban Cu balances in a comprehensive and transparent form. The main difference between Cu in the two cities appears to be the stock: Vienna seems close to saturation with 180 kilograms per capita (kg/cap) and a growth rate of 2% per year. In contrast, the Taipei stock of 30 kg/cap grows rapidly by 26% per year. Even though most Cu is recycled in both cities, bottom ash from municipal solid waste incineration represents an unused Cu potential accounting for 1% to 5% of annual demand. Nonpoint emissions are predominant; up to 50% of the loadings into the sewer system are from nonpoint sources. The results of this research are instrumental for the design of the Cu metabolism in each city. The outcomes serve as a base for identification and recovery of recyclables as well as for directing nonrecyclables to appropriate sinks, avoiding sensitive environmental pathways. The methodology applied is well suited for city benchmarking if sufficient data are available.

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

Association between polymorphisms in the csrRS two-component regulatory system and invasive group A streptococcal infection - J.-N. Lin; L.-L. Chang; C.-H. Lai; H.-H. Lin; Y.-H. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

More insights into early brain development through statistical analyses of eigen-structural elements of diffusion tensor imaging using multivariate adaptive regression splines - Yasheng Chen; Hongtu Zhu; Hongyu An; Diane Armao; Dinggang Shen; John H. Gilmore; Weili Lin (Brain Structure and Function, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

An emerging role of PARK2 in cancer - Liang Xu; De-chen Lin; Dong Yin; H. Phillip Koeffler (Journal of Molecular Medicine, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Role of HO-1 in the Arsenite-Induced Neurotoxicity in Primary Cultured Cortical Neurons - Y. C. Teng; Y. I. Tai; Y. H. Lee; A. M. Y. Lin (Molecular Neurobiology, 2013)

Preladenant, a selective adenosine A2A receptor antagonist, is not associated with QT/QTc prolongation - Z. Wang; F. Xuan; W. H. Lin; M. D. Troyer; A. Tendolkar; D. L. Cutler (European Journal of Clinical Pharmacology, 2013)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

Nyamiviridae: Proposal for a new family in the order Mononegavirales - Jens H. Kuhn; Sadia Bekal; Yíngyún Caì; Anna N. Clawson; Leslie L. Domier; Marieke Herrel; Peter B. Jahrling; Hideki Kondo; Kris N. Lambert; Kathie A. Mihindukulasuriya; Norbert Nowotny; Sheli R. Radoshitzky; et al. (Archives of Virology, 2013)

Temporal and spectral characterization of the photosynthetic reaction center from Heliobacterium modesticaldum - Adrien Chauvet; Josephine Sarrou; Su Lin; Steven P. Romberger; John H. Golbeck; Sergei Savikhin; Kevin E. Redding (Photosynthesis Research, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Augmenting satellite precipitation estimation with lightning information - Majid Mahrooghy; Valentine G. Anantharaj; Nicolas H. Younan; Walter A. Petersen; Kuo-Lin Hsu; Ali Behrangi; James Aanstoos (International Journal of Remote Sensing, 2013)

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Role of K1 capsule antigen in cirrhotic patients with Escherichia coli spontaneous bacterial peritonitis in southern Taiwan - M. C. Wang; W. H. Lin; C. C. Tseng; A. B. Wu; C. H. Teng; J. J. Yan; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Seismic health monitoring of RC frame structures using smart aggregates - Wen-I Liao; C. H. Lin; J. S. Hwang; G. Song (Earthquake Engineering and Engineering Vibration, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Water quality associated public health risk in Bo, Sierra Leone - David H. Jimmy; Abu J. Sundufu; Anthony P. Malanoski; Kathryn H. Jacobsen; Rashid Ansumana; Tomasz A. Leski; Umaru Bangura; Alfred S. Bockarie; Edries Tejan; Baochuan Lin; David A. Stenger (Environmental Monitoring and Assessment, 2013)

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

Analysis of carbamazepine serum by differential pulse voltammetry (DPV) and comparison with fluorescence polarization immunoassay (FPIA): an animal study - W. Y. Lin; M. L. Pan; H. Y. Wang; Y. O. Su; P. W. Huang (Medicinal Chemistry Research, 2012)

Comparison of point and array-computed rotations for the TAIGER explosions of 4 March 2008 - Lauren M. Kendall; Charles A. Langston; W. H. K. Lee; C. J. Lin; C. C. Liu (Journal of Seismology, 2012)

Effects of rotation motions on strong-motion data - H. C. Chiu; F. J. Wu; C. J. Lin; H. C. Huang; C. C. Liu (Journal of Seismology, 2012)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

Effect of Carrier Gas Properties on Aerosol Distribution in a CT-based Human Airway Numerical Model - Shinjiro Miyawaki; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Purification of the photosynthetic reaction center from Heliobacterium modesticaldum - Iosifina Sarrou; Zahid Khan; John Cowgill; Su Lin; Daniel Brune; Steven Romberger; John H. Golbeck; Kevin E. Redding (Photosynthesis Research, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Correlating recurrent radon precursors with local earthquake magnitude and crust strain near the Chihshang fault of eastern Taiwan - T. Kuo; C. Lin; C. Su; C. Liu; C. H. Lin; C. Chang; C. Chiang (Natural Hazards, 2011)

Three new species of Lentinus from northern Thailand - Samantha C. Karunarathna; Zhu L. Yang; Rui-Lin Zhao; Else C. Vellinga; A. H. Bahkali; Ekachai Chukeatirote; Kevin D. Hyde (Mycological Progress, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A Bayesian population analysis of the development of type 2 diabetes in the offspring of diabetic parents - C. W. Lin; J. H. Warram; P. Veng-Pedersen (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

Kinetic migration of isothiazolinone biocides from paper packaging to Tenax and Porapak - Q.-B. Lin; T.-J. Wang; H. Song; R.-Z. Wang (Food Additives & Contaminants: Part A, 2011)

A numerical simulation of the effect of the number concentration of cloud droplets on Typhoon Chanchu - WenShi Lin; Suishan Xu; C.-H. Sui (Meteorology and Atmospheric Physics, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Determination of silver in nano-plastic food packaging by microwave digestion coupled with inductively coupled plasma atomic emission spectrometry or inductively coupled plasma mass spectrometry - Q.-B. Lin; B. Li; H. Song; H.-J. Wu (Food Additives & Contaminants: Part A, 2011)

Migration of silver from nanosilver–polyethylene composite packaging into food simulants - H. Song; B. Li; Q.-B. Lin; H.-J. Wu; Y. Chen (Food Additives & Contaminants: Part A, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms - A. H. M. Selim Reza; Jiin-Shuh Jean; Huai-Jen Yang; Ming-Kuo Lee; Hua-Fen Hsu; Chia-Chuan Liu; Yao-Chang Lee; Jochen Bundschuh; Kao-Hong Lin; Chi-Yu Lee (Environmental Geochemistry and Health, 2011)

The California Neighborhoods Data System: a new resource for examining the impact of neighborhood characteristics on cancer incidence and outcomes in populations - Scarlett Lin Gomez; Sally L. Glaser; Laura A. McClure; Sarah J. Shema; Melissa Kealey; Theresa H. M. Keegan; William A. Satariano (Cancer Causes & Control, 2011)

New cyclitol derivative from a sponge Sarcotragus species - Yonghong Liu; Jee H. Jung; Tunhai Xu; Lijuan Long; Xiuping Lin; Hao Yin; Bin Yang; Xue-Feng Zhou; Xianwen Yang (Natural Product Research, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Manganese Superoxide Dismutase Deficiency Exacerbates Ischemic Brain Damage Under Hyperglycemic Conditions by Altering Autophagy - Suresh L. Mehta; Yanling Lin; Wenge Chen; Fengshan Yu; Luyi Cao; Qingping He; Pak H. Chan; P. Andy Li (Translational Stroke Research, 2011)

Papillary thyroid cancer incidence rates vary significantly by birthplace in Asian American women - Pamela L. Horn-Ross; Laura A. McClure; Ellen T. Chang; Christina A. Clarke; Theresa H. M. Keegan; Rudolph P. Rull; Thu Quach; Scarlett Lin Gomez (Cancer Causes & Control, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Interval-fuzzy stochastic optimization for regional energy systems planning and greenhouse-gas emission management under uncertainty—a case study for the Province of Ontario, Canada - Q. G. Lin; G. H. Huang (Climatic Change, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

Analysis of isothiazolinone biocides in paper for food packaging by ultra-high-performance liquid chromatography–tandem mass spectrometry - Q.-B. Lin; T.-J. Wang; H. Song; B. Li (Food Additives & Contaminants: Part A, 2010)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Numerical Study of High-Frequency Oscillatory Air Flow and Convective Mixing in a CT-Based Human Airway Model - Jiwoong Choi; Guohua Xia; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2010)

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Epac stimulation induces rapid increases in connexin43 phosphorylation and function without preconditioning effect - Nicolas Duquesnes; Mickael Derangeon; Mélanie Métrich; Alexandre Lucas; Philippe Mateo; Lin Li; Eric Morel; Frank Lezoualc’h; Bertrand Crozatier (Pflügers Archiv - European Journal of Physiology, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

Dual bio-responsive gene delivery via reducible poly(amido amine) and survivin-inducible plasmid DNA - Ran Namgung; Jonathan H. Brumbach; Ji Hoon Jeong; James W. Yockman; Sung Wan Kim; Chao Lin; Zhiyuan Zhong; Jan Feijen; Johan F. J. Engbersen; Won Jong Kim (Biotechnology Letters, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Airway Wall Stiffening Increases Peak Wall Shear Stress: A Fluid–Structure Interaction Study in Rigid and Compliant Airways - Guohua Xia; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2010)

Veterinary antibiotic sorption to agroforestry buffer, grass buffer and cropland soils - Bei Chu; Keith W. Goyne; Stephen H. Anderson; Chung-Ho Lin; Ranjith P. Udawatta (Agroforestry Systems, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Tri-directional shaking table tests of vibration sensitive equipment with static dynamics interchangeable-ball pendulum system - C. S. Tsai; Yung-Chang Lin; Wen-Shin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2010)

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

Cocaine craving and use during daily life - Kenzie L. Preston; Massoud Vahabzadeh; John Schmittner; Jia-Ling Lin; David A. Gorelick; David H. Epstein (Psychopharmacology, 2009)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Molecular characterization of two potato virus S isolates from late-blight-resistant genotypes of potato (Solanum tuberosum) - Y. H. Lin; K. L. Druffel; J. Whitworth; M. J. Pavek; Hanu R. Pappu (Archives of Virology, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

The importance of myocardial amino acids during ischemia and reperfusion in dilated left ventricle of patients with degenerative mitral valve disease - A. Venturini; R. Ascione; H. Lin; E. Polesel; G. D. Angelini; M.-S. Suleiman (Molecular and Cellular Biochemistry, 2009)

Spatio‐temporal variation in the elemental compositions of otoliths of southern bluefin tuna Thunnus maccoyii in the Indian Ocean and its ecological implication - C. H. Wang; Y. T. Lin; J. C. Shiao; C. F. You; W. N. Tzeng (Journal of Fish Biology, 2009)
The elements Na, Mg, Mn, Ca, Sr and Ba in otoliths of southern bluefin tuna Thunnus maccoyii , collected from their feeding ground in the central Indian Ocean and spawning ground between southern Java and north‐western Australia were measured by laser‐ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) and compared among sampling locations and developmental stages. The Na, Mg and Mn to Ca concentration ratios were significantly higher at the larval stage than at the adult stage, and the ratio reached a peak at the first inflection point of the otolith, mean ± s.d. 43·3 ± 4·9 days after hatching and decreased sharply to a low level thereafter. The temporal change of the elements:Ca ratios in the first inflection point corresponded to the life stage transition from larva to juvenile, indicating that the uptake rate of elements from ambient waters was significantly influenced by the ontogenetic change in the fish. The elemental composition at the otolith edge differed significantly in sub‐adults on the feeding grounds and adults on the spawning grounds. Thus, the otolith elemental composition can be used as a biological tracer to study the time of the ontogenetic shift and to reconstruct the past migratory environmental history of T. maccoyii . In addition, the elemental composition of the otolith core of the adult was similar between feeding and spawning grounds, indicating that the fish in the Indian Ocean had the same larval origin, which is consistent with the single spawning population hypothesis.

A Two-Step Infinite α-Cuts Fuzzy Linear Programming Method in Determination of Optimal Allocation Strategies in Agricultural Irrigation Systems - H. W. Lu; G. H. Huang; Y. P. Lin; L. He (Water Resources Management, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Accumulation of H2O2 in xylem fluids of cucumber stems during ASM-induced systemic acquired resistance (SAR) involves increased LOX activity and transient accumulation of shikimic acid - T. -C. Lin; H. Ishii (European Journal of Plant Pathology, 2009)

Mathematical modeling and full-scale shaking table tests for multi-curve buckling restrained braces - C. S. Tsai; Yungchang Lin; Wenshin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Abnormal pain response in pain-sensitive opiate addicts after prolonged abstinence predicts increased drug craving - Zhen-Yu Ren; Jie Shi; David H. Epstein; Jun Wang; Lin Lu (Psychopharmacology, 2009)

A study of the microphysical processes in a numerically simulated heavy snowfall event in North China: the sensitivity of different snow intercept parameters - Wenshi Lin; Jinping Meng; C.-H. Sui; Weiguang Meng; Jiangnan Li (Meteorology and Atmospheric Physics, 2009)

Colour variation is incongruent with mitochondrial lineages: cryptic speciation and subsequent diversification in a Gulf of California reef fish (Teleostei: Blennioidei) - H‐C. LIN; C. SÁNCHEZ‐ORTIZ; P. A. HASTINGS (Molecular Ecology, 2009)
The Gulf of California endemic reef fish, Acanthemblemaria crockeri (Blennioidei, Chaenopsidae), reportedly has two colour morphs, one with melanic lateral spots (‘Gulf’ morph) and one with orange spots (‘Cape’ morph). In this study, we recorded colour morph in both males and females and collected mitochondrial DNA sequence data for cytochrome c oxidase I (COI) and tRNA‐Pro/D‐loop of specimens from throughout the Gulf to explore the genetic basis of the colour morphs. Two highly divergent (HKY + I distance = 11.9% for COI), reciprocally monophyletic lineages were identified, consistent with the presence of two parapatric species. A 30‐km gap between the distributions of mitochondrial lineages roughly corresponds to a hypothesized former seaway across the Baja California peninsula north of La Paz, although the estimated divergence time (1.84 million years ago) is more recent than the hypothetical seaway (3–4 million years ago). Surprisingly, the distribution of mitochondrial species is not congruent with the distribution of either male or female colour morphs. Our analysis also revealed significant population differentiation within both species and no shared haplotypes among populations. The northern Gulf species includes four populations (NB, CB, NM and CM) corresponding to northern and central Baja and northern and central mainland sites, while the Cape species includes two populations (SB and SM) corresponding to the Baja and mainland sides of the southern Gulf. The NB/CB division corresponds to a hypothesized Plio–Pleistocene mid‐peninsular seaway. The level of genetic divergence documented in this lineage is extraordinary for a marine fish with a pelagic larval stage within a semi‐enclosed basin.

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Psychosocial stress after reactivation of drug-related memory impairs later recall in abstinent heroin addicts - Li-Yan Zhao; Xiao-Li Zhang; Jie Shi; David H. Epstein; Lin Lu (Psychopharmacology, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Identification of wheat line YW243 on comprehensive resistance to several diseases by pathogens and molecular markers - H. Xie; Z. Lin; Z. Zhang; L. Du; Z. Xin; Y. Ma; X. Ye; X. Chen (Cereal Research Communications, 2008)

Identification and expression characterization of pepsinogen A in orange‐spotted grouper, Epinephelus coioides - S. Z. Feng; W. S. Li; H. R. Lin (Journal of Fish Biology, 2008)
To understand the molecular mechanisms associated with digestive physiology of the stomach of orange‐spotted grouper Epinephelus coioides , a cDNA library was constructed and 331 expressed sequence tags (EST) were generated and annotated. About 37·17% of 226 identified ESTs were possibly related to digestive enzymes. Two type‐A pepsinogens differing in putative isoelectric point were identified and characterized for the first time in E. coioides . The complete cDNAs were 1312 and 1314 bp in length, and the deduced polypeptide sequences comprised 376 and 377 amino acids, respectively. Both genes consisted of eight introns of various lengths. Alignment and a phylogenetic tree based on the amino acid sequences of pepsins indicated that pepsin A1 and A2 could be classified into two different subtypes. Northern blot hybridization showed that there were two forms of transcripts for pepsinogen A1 and three for pepsinogen A2. Reverse transcription‐PCR (RT‐PCR) followed by Southern blot analysis revealed that two type‐A pepsinogen mRNAs were present in the adult stomach tissue, and pepsinogen A2 was also detectable in the mid‐intestine. Furthermore, pepsinogen A1 transcript was first detected at 29 days post‐hatching, while pepsinogen A2 was continuously expressed through hatching to adult fish. These results imply that transcriptional regulation and physiological function of the two type‐A pepsinogens may be different.

Plasma vitamins E and A and risk of bladder cancer: a case–control analysis - Dong Liang; Jie Lin; H. Barton Grossman; Jing Ma; Bo Wei; Colin P. Dinney; Xifeng Wu (Cancer Causes & Control, 2008)

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

Yersinia enterocolitica infection in diarrheal patients - H. Zheng; Y. Sun; S. Lin; Z. Mao; B. Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Treatment of polluted river water by a gravel contact oxidation system constructed under riverbed - D. F. Juang; W. P. Tsai; W. K. Liu; J. H. Lin (International Journal of Environmental Science and Technology, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Sustainable Construction Case History: Fly Ash Stabilization of Recycled Asphalt Pavement Material - Lin Li; Craig H. Benson; Tuncer B. Edil; Bulent Hatipoglu (Geotechnical and Geological Engineering, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Expression and immunogenic comparison of VP2 and VP3 from marine birnavirus - H‐J Xu; J‐G Lin; C‐X Zhang; S Suzuki (Journal of Fish Diseases, 2008)
The coding regions for the major epitopes of structural protein VP2 ( vp2e ) and structural protein VP3 were amplified from marine birnavirus (MABV) cDNA and efficiently expressed as glutathione S‐transferase (GST) fusion proteins in Escherichia coli . Polyclonal antibodies against VP2e and VP3 were raised in rabbits and fish using the purified proteins of GST/VP2e and GST/VP3. The rabbit anti‐serum against VP3 was more sensitive than the rabbit anti‐VP2e serum in detecting virus in MABV‐infected fish, while fish anti‐VP2e serum showed a stronger neutralization response than fish anti‐VP3 serum.

Early developmental and stress responsive ESTs from mungbean, Vigna radiata (L.) Wilczek, seedlings - Li-Ru Chen; Albert H. Markhart; S. Shanmugasundaram; Tsai-Yun Lin (Plant Cell Reports, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Automatic relative radiometric normalization using iteratively weighted least square regression - L. Zhang; L. Yang; H. Lin; Mingsheng Liao (International Journal of Remote Sensing, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Salmonellae and Campylobacters in Household and Stray Dogs in Northern Taiwan - H.-J. Tsai; H.-C. Huang; C.-M. Lin; Y.-Y. Lien; C.-H. Chou (Veterinary Research Communications, 2007)

Fracture network characteristics of a deep borehole in the Table Mountain Group (TMG), South Africa - L. Lin; H. Jia; Y. Xu (Hydrogeology Journal, 2007)

In vitro flowering of green and albino Dendrocalamus latiflorus - Choun-Sea Lin; C. J. Liang; H. W. Hsaio; M. J. Lin; W. C. Chang (New Forests, 2007)

Dissipation of Pendimethalin in the Garlic (Allium sativum L.) under Subtropical Condition - H. T. Lin; S. W. Chen; C. J. Shen; C. Chu (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Urinary tract diseases and bladder cancer risk: a case–control study - Manisha Jhamb; Jie Lin; Rebecca Ballow; Ashish M. Kamat; H. Barton Grossman; Xifeng Wu (Cancer Causes & Control, 2007)

Image processing of FORMOSAT‐2 data for monitoring the South Asia tsunami - C.‐C. Liu; J.‐G. Liu; C.‐W. Lin; A.‐M. Wu; S.‐H. Liu; C.‐L. Shieh (International Journal of Remote Sensing, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Accumulation of additive effects generates a strong photoperiod sensitivity in the extremely late-heading rice cultivar ‘Nona Bokra’ - Y. Uga; Y. Nonoue; Z. W. Liang; H. X. Lin; S. Yamamoto; U. Yamanouchi; M. Yano (Theoretical and Applied Genetics, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

A dual site study of the rainwater chemistry within the Western Pacific region - K. M. Wai; S. H. Wang; P. A. Tanner; N. H. Lin (Journal of Atmospheric Chemistry, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)

Responses of Metapopulation Dynamics to Two Different Kinds of Habitat Destruction Caused by Human Activities - H. Y. Liu; Z. S. Lin; T. Wen (Plant Ecology, 2006)

Isolation of Endophytic Actinomycetes from Different Cultivars of Tomato and their Activities Against Ralstonia solanacearum in Vitro - H. M. Tan; L. X. Cao; Z. F. He; G. J. Su; B. Lin; S. N. Zhou (World Journal of Microbiology and Biotechnology, 2006)

Multifunctionality of paddy fields in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan (Paddy and Water Environment, 2006)

Serum Heat Shock Protein (HSP70) and Its Antibody (Anti-HSP70) Levels in Male Foundry Workers in Taiwan - C.-J. Chen; H.-J. Wen; S.-H. Liu; M.-S. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Pressure effect on the electronic structure of iron in (Mg,Fe)(Si,Al)O3 perovskite: a combined synchrotron Mössbauer and X-ray emission spectroscopy study up to 100 GPa - J. Li; W. Sturhahn; J. M. Jackson; V. V. Struzhkin; J. F. Lin; J. Zhao; H. K. Mao; G. Shen (Physics and Chemistry of Minerals, 2006)

Scaling and organization of electroencephalographic background activity and alpha rhythm in healthy young adults - D. C. Lin; A. Sharif; H. C. Kwan (Biological Cybernetics, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Novel polymorphic microsatellites for studying genetic diversity of red Asian arowanas - G. H. Yue; Z. Y. Zhu; G. Lin; L. C. Lo; F. Feng (Conservation Genetics, 2006)

Detection of Hong Kong 97-like H5N1 influenza viruses from eggs of Vietnamese waterfowl - Y. Li; Z. Lin; J. Shi; Q. Qi; G. Deng; Z. Li; X. Wang; G. Tian; H. Chen (Archives of Virology, 2006)

Tissue Accumulation of Arsenic Compounds in Aquacultural and Wild Mullet (Mugil cephalus) - C.-W. Liu; K.-H. Lin; C.-S. Jang (Bulletin of Environmental Contamination and Toxicology, 2006)

CYP Induction-Mediated Drug Interactions: in Vitro Assessment and Clinical Implications - Jiunn H. Lin (Pharmaceutical Research, 2006)

Organic Matter Stable Isotope (δ13C, δ15N) Response to Historical Eutrophication of Lake Taihu, China - Jinglu Wu; Lin Lin; Michael K. Gagan; Gerhard H. Schleser; Sumin Wang (Hydrobiologia, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Ancient paddy soils from the Neolithic age in China’s Yangtze River Delta - Z. H. Cao; J. L. Ding; Z. Y. Hu; H. Knicker; I. Kögel-Knabner; L. Z. Yang; R. Yin; X. G. Lin; Y. H. Dong (The Science of Nature, 2006)

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Reduced TCOF1 mRNA level in a rhesus macaque with Treacher Collins-like syndrome: further evidence for haploinsufficiency of treacle as the cause of disease - Kathryn H. Shows; Christy Ward; Laura Summers; Lin Li; Gregory R. Ziegler; Andrew G. Hendrickx; Rita Shiang (Mammalian Genome, 2006)

Probability density estimation in stochastic environmental models using reverse representations - E. van den. Berg; A. W. Heemink; H. X. Lin; J. G. M. Schoenmakers (Stochastic Environmental Research and Risk Assessment, 2006)

The Complete Mitochondrial Genome Sequence and Characterization of Single-Nucleotide Polymorphisms in the Control Region of the Asian Seabass (Lates calcarifer) - G. Lin; L. C. Lo; Z. Y. Zhu; F. Feng; R. Chou; G. H. Yue (Marine Biotechnology, 2006)

Implicit solvent simulation models for biomembranes - Grace Brannigan; Lawrence C.-L. Lin; Frank L. H. Brown (European Biophysics Journal, 2006)

Use of a fluorescent membrane probe to identify zooxanthellae in hospite among dissociated endoderm cell culture from coral - C.-S. Chen; H.-P. Lin; C.-C. Yeh; L.-S. Fang (Protoplasma, 2005)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Genetic and physical mapping of Pi36(t), a novel rice blast resistance gene located on rice chromosome 8 - X. Q. Liu; L. Wang; S. Chen; F. Lin; Q. H. Pan (Molecular Genetics and Genomics, 2005)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

Interconversion Pharmacokinetics of Simvastatin and its Hydroxy Acid in Dogs: Effects of Gemfibrozil - Thomayant Prueksaritanont; Yue Qiu; Lillian Mu; Kimberly Michel; Janice Brunner; Karen M. Richards; Jiunn H. Lin (Pharmaceutical Research, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Roles of Hemodynamic Forces in Vascular Cell Differentiation - Gordon M. Riha; Peter H. Lin; Alan B. Lumsden; Qizhi Yao; Changyi Chen (Annals of Biomedical Engineering, 2005)

Etoposide (VP-16) sensitizes p53-deficient human non-small cell lung cancer cells to caspase-7-mediated apoptosis - C.-C. Chiu; C.-H. M. Y. Lin; K. Fang (Apoptosis, 2005)

Orographic effects on a conditionally unstable flow over an idealized three-dimensional mesoscale mountain - S.-H. Chen; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Histology and histochemical enzyme‐staining patterns of major immune organs in Epinephelus malabaricus - H.‐T. Lin; H.‐Y. Lin; H.‐L. Yang (Journal of Fish Biology, 2005)
The histological architecture of major immune organs in the Malabar grouper Epinephelus malabaricus was investigated. The novel characteristics such as melanomacrophage centres (MMCs) appeared in the thymus and lymphopoietic tissue formed as foci in the head kidney. Leukocyte distribution in organs was identified by enzyme histochemistry. β‐glucuronidase (BG) reactive cells in the cortex region of the thymus were botryoidally aggregated. Both acid phosphatase (AcP) and BG reactive cells concentrated within the specialized lymphopoietic foci in the head kidney, suggesting that the foci might be functional. Primitive histological characters of immunity were observed in the spleen. Although leukocyte aggregation was demonstrated in the spleen, additional enzyme histochemistry indicated that the aggregate might not be the equivalent of white pulp found in other vertebrates. The histological evidence did not support intestinal involvement in the immune system: there was no demonstrable gut associated lymphoid tissue. The limited distribution in the cortex and medulla boundary and the condensed format of the lymphocytes suggests a functional role for the MMC in the thymus of E. malabaricus . The MMC appearance in the thymus of a teleost was unusual.

Molecular Genetic Analysis of QTLs for Ferulic Acid Content in Dried Straw of Rice (Oryza sativa L.) - Yanjun Dong; E. Tsuzuki; H. Kamiunten; Dongzhi Lin; H. Terao; M. Matsuo; Shihua Cheng (Biochemical Genetics, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

Fisheries of two tropical lagoons in Ghana, West Africa - H. R. Dankwa; J. M. Shenker; J. Lin; P. K. Ofori‐Danson; Y. Ntiamoa‐Baidu (Fisheries Management and Ecology, 2004)
The fisheries of two coastal lagoons, Keta and Songor, were studied as part of Ghana Coastal Wetlands Management Project (GCWMP) aimed at sustainable exploitation of wetland resources. Fish samples were obtained with seine nets and cast net as well as from local fishermen. Water quality parameters (pH, dissolved oxygen, temperature and turbidity) were similar in the two lagoons, except for salinity, which was significantly different ( P Sarotherodon melanotheron Rüppell, and the redchin tilapia, Tilapia guineensis (Bleeker), being the most important commercial fishes in both lagoons. The number of individuals for each species in Songor Lagoon were far more abundant, with densities several orders of magnitude higher than in Keta Lagoon. However, both species were significantly larger ( P S. melanotheron and T. guineensis respectively. Over‐fishing, use of small‐size mesh nets, limited mixing of marine and fresh water were some of the factors limiting fish production in both lagoons.

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Interactions of Human P-glycoprotein with Simvastatin, Simvastatin Acid, and Atorvastatin - Jerome H. Hochman; Nicole Pudvah; Julia Qiu; Masayo Yamazaki; Cuyue Tang; Jiunn H. Lin; Thomayant Prueksaritanont (Pharmaceutical Research, 2004)

Identification of a 98-kb DNA segment containing the rice Eui gene controlling uppermost internode elongation, and construction of a TAC transgene sublibrary - Y.-H. Xu; Y.-Y. Zhu; H.-C. Zhou; Q. Li; Z.-X. Sun; Y.-G. Liu; H.-X. Lin; Z.-H. He (Molecular Genetics and Genomics, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

Predicted ATP-binding cassette systems in the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; H. Wang; R. W. Hammond; R. Jomantiene; Q. Liu; S. Lin; B. A. Roe; R. E. Davis (Molecular Genetics and Genomics, 2004)

Kinetic Studies on the Effects of Organophosphorus Pesticides on the Growth of Microcystis aeruginosa and Uptake of the Phosphorus Forms - P.-J. Zhou; H. Shen; J. Lin; L.-R. Song; Y.-D. Liu; Z.-B. Wu (Bulletin of Environmental Contamination and Toxicology, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Potential biological control of weeds in rice fields by allelopathy of dwarf lilyturf plants - Dongzhi Lin; Eiji Tsuzuki; Yanjun Dong; H. Terao; T.D. Xuan (BioControl, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Pilot point temperature regulation for thermal lesion control during ultrasound thermal therapy - H. -L. Liu; Y. -Y. Chen; J. -Y. Yen; W. -L. Lin (Medical & Biological Engineering & Computing, 2004)

Detection and classification of allexiviruses from garlic in China - J. Chen; H.-Y. Zheng; J. F. Antoniw; M. J. Adams; J.-P. Chen; L. Lin (Archives of Virology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

QTLs for Na+ and K+ uptake of the shoots and roots controlling rice salt tolerance - H. X. Lin; M. Z. Zhu; M. Yano; J. P. Gao; Z. W. Liang; W. A. Su; X. H. Hu; Z. H. Ren; D. Y. Chao (Theoretical and Applied Genetics, 2004)

Nonlinear Time Series Analysis of Volcanic Tremor Events Recorded at Sangay Volcano, Ecuador - K. I. Konstantinou; C. H. Lin (Pure and Applied Geophysics, 2004)

QSARs for Predicting the Toxicity of Mixtures Containing Polar Narcotic Chemicals - Z. Lin; K. Yin; C. Wu; L. Wang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Cariporide enhances lactate clearance upon reperfusion but does not alter lactate accumulation during global ischaemia - H. Lin; M.-S. Suleiman (Pflügers Archiv - European Journal of Physiology, 2003)

Outbreaks of an iridovirus disease in maricultured large yellow croaker, Larimichthys crocea (Richardson), in China - X H Chen; K B Lin; X W Wang (Journal of Fish Diseases, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Genetic evidence for a role of phospholipase C at the budding yeast kinetochore - N. DeLillo; C. Romero; H. Lin; A. Vancura (Molecular Genetics and Genomics, 2003)

Detection and analysis of QTLs for ferrous iron toxicity tolerance in rice, Oryza sativa L. - Jian-lin Wan; Hu-qu Zhai; Jian-min Wan; H. Ikehashi (Euphytica, 2003)

Visibility Variation with Air Qualities in the Metropolitan Area in Southern Taiwan - Ying I. Tsai; Yi H. Lin; Suen Z. Lee (Water, Air, & Soil Pollution, 2003)

Development of Linum flavum hairy root cultures for production of coniferin - Han-wei Lin; Kian H. Kwok; Pauline M. Doran (Biotechnology Letters, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Trace Metals in Candle Smoke - T.-S. Lin; F.-M. Shen; J.-L. Chen; M.-H. Yang (Bulletin of Environmental Contamination and Toxicology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Yield Surface of Mu-San Sandstone by Hollow Cylinder Tests - D.-H. Lee; C. H. Juang; H.-M. Lin (Rock Mechanics and Rock Engineering, 2002)

Phospholipase C interacts with Sgd1p and is required for expression of GPD1 and osmoresistance in Saccharomyces cerevisiae - H. Lin; P. Nguyen; A. Vancura (Molecular Genetics and Genomics, 2002)

Genetic dissection of a genomic region for a quantitative trait locus, Hd3, into two loci, Hd3a and Hd3b, controlling heading date in rice - L. Monna; H. Lin; S. Kojima; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2002)

Modulation of calcium balance in tilapia larvae ( Oreochromis mossambicus ) acclimated to low-calcium environments - Chou M.-Y.; Lu F.-I.; Lin H.-C.; Hwang P.-P.; Yang C.-H. (Journal of Comparative Physiology B, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Plasmids carrying cloned fragments of RF DNA from the filamentous phage φLf can be integrated into the host chromosome via site-specific integration and homologous recombination - N.-T. Lin; R.-Y. Chang; S.-J. Lee; Y.-H. Tseng (Molecular Genetics and Genomics, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Nutritive quality and morphological development under partial shade of some forage species with agroforestry potential - C. H. Lin; M. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 2001)

Development of the Fragment Constant Method for Estimating the Partition Coefficients of Nonionic Organic Mixtures - Z. Lin, H. Yu, S. Gao, J. Cheng, L. Wa (Archives of Environmental Contamination and Toxicology, 2001)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Environmental Exposure to Polycyclic Aromatic Hydrocarbons and Total Suspended Particulates in a Taiwanese Temple - T-C. Lin; F-H. Chang; J-H. Hsieh; H-R. Chao; M-R. Chao (Bulletin of Environmental Contamination and Toxicology, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Functional Asymmetry of the Sodium- d -Glucose Cotransporter Expressed in Yeast Secretory Vesicles - M.A. Firnges; J.-T. Lin; R.K.-H. Kinne (The Journal of Membrane Biology, 2001)

Surveys of Volatile Organic Compounds in Soil and Groundwater at Industrial Sites in Taiwan - M.-C. T. Kuo, C.-M. Chen, C. H. Lin, H. C (Bulletin of Environmental Contamination and Toxicology, 2000)

Characterization and detection of epistatic interactions of 3 QTLs, Hd1, Hd2, and Hd3, controlling heading date in rice using nearly isogenic lines - H. X. Lin; T. Yamamoto; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2000)

Differences in size and growth rates of male and female migrating Japanese eels in Pearl River, China - W. N. Tzeng; H. R. Lin; C. H. Wang; S. N. Xu (Journal of Fish Biology, 2000)
The Sr/Ca ratios in otoliths of silver Japanese eels Anguilla japonica , in Pearl River, China, indicated that both sexes did not stay in brackish water and grew in fresh water from the glass eel stage until spawning migration. This did not support the hypothesis that females tended to distribute upstream and males might be restricted to estuaries. The back‐calculated total length of males at glass eel stage was not significantly different from that of females, indicating that the hypothesis that small glass eels became males and larger ones became females may not be true. The mean (±S.D.) age and total length of males at migration were 6·4±1·6 years and 48·3±4·5 cm, which were significantly smaller than for females, 8·3±1·6 years and 61·4±4·1 cm. The age of migration was related inversely to growth rate for both sexes. Growth parameters of the von Bertalanffy growth equation were K =0·21 cm year°1, L ∞ =55·7 cm and t o =‐0·55 year for males and K =0·14 cm year −1 , L ∞ =77·5 cm and t o =‐0·60 year for females. The difference in asymptotic length ( L ∞ ) between males and females may be because females postpone migration to achieve larger size for maximizing reproductive success.

TGFβ1 stimulates the secretion of matrix metalloproteinase 2 (MMP2) and the invasive behavior in human ovarian cancer cells, which is suppressed by MMP inhibitor BB3103 - Sui-Wen Lin; Ming-Ting Lee; Ferng-Chun Ke; Ping-Ping H. Lee; Chang-Jen Huang; Margot M. Ip; Lily Chen; Jiuan-Jiuan Hwang (Clinical & Experimental Metastasis, 2000)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Maternal transfer of cadmium tolerance in larval Oreochromis mossambicus - H. C. Lin; S.C Hsu; P.P. Hwang (Journal of Fish Biology, 2000)
Exposing female tilapia to Cd did not affect reproduction and egg quality, nor the survival of their offspring. The LT 50 of Cd‐exposed larvae (within 24 h post hatching) from Cd‐treated female Oreochromis mossambicus (mean ±S.E.=10·9±0·5 days, n =4) was greater than that of Cd‐exposed larvae from control females (6·9± 1·2 days, n =4). A substantial amount of metallothionein mRNA (MT mRNA) was found in both oocytes and newly hatched larvae from Cd‐treated females, but MT mRNA levels were low in newly fertilized eggs. The amount of MT mRNA was very low in all these stages in the control group. Cadmium could not be detected at any stage for either control or Cd‐treated group, and metallothionein protein levels were also very low in both groups. The early appearance of MT mRNA in oocytes and newly hatched larvae from Cd‐treated females may result in early translation after hatching and explain their tolerance to Cd.

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Artifact reduction in electrogastrogram based on empirical mode decomposition method - H. Liang; Z. Lin; R. W. McCallum (Medical & Biological Engineering & Computing, 2000)

Mineralization of organic sulfur and its importance as a reservoir of plant-available sulfur in upland soils of north China - W. Zhou; S. T. Li; H. Wang; P. He; B. Lin (Biology and Fertility of Soils, 1999)

Type-1c glycogen storage disease is not caused by mutations in the glucose-6-phosphate transporter gene - B. Lin; H. Hiraiwa; C.-J. Pan; R.C. Nordlie; J.Y. Chou (Human Genetics, 1999)

Type-1c glycogen storage disease is not caused by mutations in the glucose-6-phosphate transporter gene - B. Lin; H. Hiraiwa; C.-J. Pan; R.C. Nordlie; J.Y. Chou (Human Genetics, 1999)

Agricultural Chemicals in the Alluvial Aquifer of a Typical County of the Arkansas Delta - H. S. Lin; H. D. Scott; K. F. Steele; H. I. Inyang (Environmental Monitoring and Assessment, 1999)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

Probing Transmembrane Topology of the High-Affinity Sodium/Glucose Cotransporter (SGLT1) with Histidine-Tagged Mutants - J.-T. Lin; J. Kormanec; D. Homerová; R.K.-H. Kinne (The Journal of Membrane Biology, 1999)

Evaluation of the Characteristics of Acid Precipitation in Taipei, Taiwan Using Cluster Analysis - N.-H. Lin; H.-M. Lee; M.-B. Chang (Water, Air, & Soil Pollution, 1999)

Soil Leaching Column Chromatographic Technique for Estimation of Leaching Behavior of Atrazine, Deethylatrazine, Deisopropylatrazine, and Hydroxyatrazine on Soil - F. Xu *, , X.-M. Liang; B. Lin; F. Su; H. Zhong; K.-W. Schramm; A. Kettrup (Bulletin of Environmental Contamination and Toxicology, 1999)

In vitro immunoregulatory effects of lithium in healthy volunteers - M. Maes; C. Song; A.-h. Lin; Rosaria Pioli; Gunter Kenis; Marta Kubera; Eugene Bosmans (Psychopharmacology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Mitochondrion‐rich cells in the embryonic yolk sac of Oreochromis mossambicus - H. C. Lin; P. P. Hwang; T. H. Lee (Journal of Fish Biology, 1999)
By removing a small amount of yolk, tilapia embryos were dechorionated successfully as early as 30 h after fertilization. Using DASPEI, a mitochondrion‐specific fluorescent stain, we were able to determine the first appearance of the mitochondrion rich cells on the surface of the yolk sac 26 h after fertilization ( c. 2 h after the beginning of gastrula stage). However, with scanning electron microscopy examination, no apical crypt could be found until 48 h after fertilization.

Phenotypic plasticity in the growth of the self‐fertilizing hermaphroditic fish Rivulus marmoratus - H.‐C. Lin; W. A. Dunson (Journal of Fish Biology, 1999)
Temperature, salinity, food ration and interactions among them had significant effects on overall growth of hatchlings of the self‐fertilizing hermaphrodite Rivulus marmoratus . Low temperature (19° C) suppressed growth. At 26° C, the treatment groups at 12 and 40‰ salinity had higher final wet masses than the group at 1‰. When provided with high food ration, individuals whose parents were provided with low food had a significantly higher specific growth rate in the first month than those whose parents were provided with high food ration. This effect was also found in the final wet masses. It appears that genetic variation in this species occurs only between strains, yet within a strain there is considerable scope for phenotypic plasticity. The combination of a fixed genotype and plastic expression, along with a suite of specialized physiological characteristics, may explain how a self‐fertilizing hermaphrodite can thrive in such an abiotically stressful and variable habitat as an estuary.

Vagal afferents from the uterus and cervix provide direct connections to the brainstem - J. J. Collins; C. E. Lin; H. R. Berthoud; R. E. Papka (Cell and Tissue Research, 1999)

Shade effects on forage crops with potential in temperate agroforestry practices - C. H. Lin; R. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 1998)

A morphological study of cells isolated from the perfused gill of dab and Atlantic salmon - S.‐H. Lin; G. A. Davidson; C. J. Secombes; A. E. Ellis (Journal of Fish Biology, 1998)
Single cell suspensions were derived from the gills of dab Limanda limanda and Atlantic salmon Salmo salar which were free from blood cell contamination. Gills were perfused with heparinized saline before the cells were liberated from their resident position using a procedure employing chelating agents and collagenase digestion. Cells were characterized using light and electron microscopy as well as histochemical staining. The results indicate that the cell types resident in the gill tissue should be capable of expressing local immune competence. Small and large lymphocytes, macrophages, neutrophils, eosinophilic granule cells, goblet cells, chloride cells and cells of unusual morphology were identified especially the presence of goblet cells apparently within epithelial‐like cells.

A SINE species from hippopotamus and its distribution among animal species - O. Nomura *, , Z.-H. Lin; Not Available Not Available; Y. Wada; H. Yasue (Mammalian Genome, 1998)

Acute and Chronic Effects of Antimony Chloride (SbCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Acute and Chronic Effects of Indium Chloride (InCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Acute and Chronic Effects of Gallium Chloride (GaCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Maturation-dependent gene expression in a conditionally transformed liver progenitor cell line - A. S. Fiorino; A. M. Diehl; H. Z. Lin; I. R. Lemischka; L. M. Reid (In Vitro Cellular & Developmental Biology - Animal, 1998)

Seasonal variation and origin of Particulate Organic Carbon in the lower Garonne River at La Reole (southwestern France) - E. Veyssy; H. Etcheber; R.G. Lin; P. Buat-Menard; E. Maneux (Hydrobiologia, 1998)

Histamine in plasma and bronchoalveolar lavage fluid during cardiac surgery: Comparison of a heparin-coated and a non-coated circuit - A. H. Lin; F. J. van Overveld; I. Rodrigus; A. Moulijn; W. A. De Backer (Inflammation Research, 1997)

Effects of cadmium on the kinetics of calcium uptake in developing tilapia larvae, Oreochromis mossambicus - M.-H. Chang; H.-C. Lin; P.P. Hwang (Fish Physiology and Biochemistry, 1997)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Fine scale mapping places DLG1, the gene encoding hDlg, telomeric to the OPA1 candidate region - Christiane Alexander; Dean G. Stathakis; Lunhui Lin; Shayan Rahman; Peter J. Bryant; Georg Auburger; Athar H. Chishti (Mammalian Genome, 1997)

Zinc status in plasma of obese individuals during glucose administration - Ming-Der Chen; Pi-Yao Lin; Wayne H. -H. Sheu (Biological Trace Element Research, 1997)

Direct shoot regeneration from excised leaf explants of in vitro grown seedlings of Alstroemeria L. - H. S. Lin; M. J. De Jeu; E. Jacobsen (Plant Cell Reports, 1997)

The pharmacokinetics and pharmacodynamics of adinazolam: multi-ethnic comparisons - Kotra Ajir; Michael Smith; Keh-Ming Lin; Dora Anderson; Inocencia Nuccio; Yanping Zheng; Russell E. Poland; Joseph C. Fleishaker; James H. Chambers (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The acetylcholine releaser linopirdine increases parietal regional cerebral blood flow in Alzheimer's disease - Christopher H. van Dyck; C. Huie Lin; Rhonda Robinson; Janet Cellar; Eileen O. Smith; J. Craig Nelson; Amy F. T. Arnsten; Paul B. Hoffer (Psychopharmacology, 1997)

Three-dimensional P-wave Velocity Structure of the Bear Valley Region of Central California - C.-H. Lin; S. W. Roecker (Pure and Applied Geophysics, 1997)

Phylogenetic analysis of feline immunodeficiency virus isolated from cats in Taiwan - G. Inada; T. Miyazawa; Y. Inoshima; M. Kohmoto; Y. Ikeda; C. -H. Liu; J. A. Lin; T. -F. Kou; T. Mikami (Archives of Virology, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

Assignment of the ARAF1 to porcine Chromosome Xpll.2-p13 by fluorescence in situ hybridization - Hiroshi Yasue; L. Adams; A. Ozawa; M. Hanazono; N. Li; Z. H. Lin; H. Kusumoto (Mammalian Genome, 1997)

Physical mapping of four RAPDs in the B chromosome of maize - B.-Y. Lin; H.-P. Chou (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Mutagenic Activity of Incense Smoke in Comparison to Formaldehyde and Acetaldehyde in Salmonella typhimurium TA102 - H. L. Chang; M. L. Kuo; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 1997)

Somatic mosaicism for deletion of the entire NF1 gene identified by FISH - Bai-Lin Wu; Richard G. Boles; Hana Yaari; Stanislawa Weremowicz; Gretchen H. Schneider; B. R. Korf (Human Genetics, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

Deletion of the carboxy-terminus of herpes simplex virus type 1 (HSV-1) glycoprotein B does not affect oligomerization, heparin-binding activity, or its ability to protect against HSV challenge - X. H. Lin; M. A. Ali; H. Openshaw; E. M. Cantin (Archives of Virology, 1996)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Trace elements and lipid peroxidation in uremic patients on hemodialysis - T. H. Lin; J. G. Chen; J. M. Liaw; J. G. Juang (Biological Trace Element Research, 1996)

Capsid protein of cucumber mosaic virus accumulates in the nuclei and at the periphery of the nucleoli in infected cells - N. -S. Lin; C. -E. Hsieh; Y. -H. Hsu (Archives of Virology, 1996)

Lead-catalyzed peroxidation of essential unsaturated fatty acid - S. J. Yiin; T. H. Lin (Biological Trace Element Research, 1995)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Complete genomic RNA sequences of cucumber mosaic virus strain NT9 from Taiwan - Y. -H. Hsu; C. -W. Wu; B. -Y. Lin; H. -Y. Chen; M. -F. Lee; C. -H. Tsai (Archives of Virology, 1995)

Different sensitivities to cadmium in tilapia larvae (Oreochromis mossambicus; teleostei) - P. P. Hwang; S. W. Lin; H. C. Lin (Archives of Environmental Contamination and Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

Consequences of pruning in morphometry of coronary vasculature - Ghassan S. Kassab; Daniel H. Lin; Yuan-Cheng B. Fung (Annals of Biomedical Engineering, 1994)

Trace elements in hair of blackfoot disease - T. C. Pan; T. H. Lin; C. L. Tseng; M. H. Yang; C. W. Huang (Biological Trace Element Research, 1993)

Simultaneous determination of Zn, Cd, Pb, and Cu in urine of patients with blackfoot disease using anodic stripping voltammetry - T. C. Pan; C. J. Horng; S. R. Lin; T. H. Lin; C. W. Huang (Biological Trace Element Research, 1993)

A new immunostimulatory complex (PICKCa) in experimental rabies: antiviral and adjuvant effects - H. X. Lin; C. Gontier; M-F. Saron; P. Perrin (Archives of Virology, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Distribution of charged pterins in nonmethanogenic archaebacteria - Xinli Lin; Robert H. White (Archives of Microbiology, 1988)

Characteristics of spontaneously produced and of virus-induced human LuKII cell interferons - Lulu A. Pickering; L. S. Lin; F. H. Sarkar (Archives of Virology, 1983)

Morbidity and mortality in workers occupationally exposed to pesticides - Donald P. Morgan; Lawrence I. Lin; Heidi H. Saikaly (Archives of Environmental Contamination and Toxicology, 1980)

Influence of insecticide exposure on thein vivo andin vitro metabolic activity of rats - T. Lin; H. W. Dorough (Archives of Environmental Contamination and Toxicology, 1974)

G6PD Toronto - J. H. Crookston; A. Yoshida; M. Lin; D. J. Booser (Biochemical Genetics, 1973)

Flavodoxin fromAzotobacter vinelandii - B. Lin; H. Bothe (Archives of Microbiology, 1972)

Elektronenmikroskopische Untersuchungen ber die Entwicklung von Coxiella burneti im Hodengewebe des Meerschweinchens - W. Lin; A. Stelzner; H. Urbach (Archives of Virology, 1969)